Magnetic tape, magnetic tape cartridge, and magnetic tape device
The magnetic tape design with controlled surface roughness and non-magnetic layers addresses off-track issues in magnetic tapes, improving drive stability and accuracy for long-term storage.
Patent Information
- Application Number
- JP2024103227
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-30
- Filing Date
- 2024-06-26
- Publication Date
- 2025-01-20
AI Technical Summary
Magnetic tapes experience operational instability during recording and reproduction due to off-track issues caused by tape width deformation, especially after long-term storage, which is exacerbated by increased track density and long-term archiving needs.
A magnetic tape design with specific surface roughness (Sci) and standard deviation (σ) parameters, along with a non-magnetic layer and back coat layer, to minimize nonlinear tape width deformation and improve head tracking accuracy.
Enhances the operational stability of magnetic tape drives by reducing off-track occurrences, ensuring accurate data recording and retrieval even after long-term storage.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic tape, a magnetic tape cartridge, and a magnetic tape device. [Background technology]
[0002] Magnetic recording media include tape-type and disk-type recording media, and tape-type magnetic recording media, that is, magnetic tapes, are primarily used for data storage applications such as data backup and archiving (see, for example, Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Special Publication No. 2016-524774 [Patent Document 2] US2019 / 0164573A1 [Patent Document 3] Patent No. 6590102 specification Summary of the Invention [Problem to be solved by the invention]
[0004] Data is usually recorded on a magnetic tape by running the magnetic tape in a magnetic tape device (commonly called a "drive") and recording data on the data band by making a magnetic head follow the data band of the magnetic tape. This forms a data track on the data band. When playing back the recorded data, the magnetic tape is run in the magnetic tape device and the magnetic head follows the data band of the magnetic tape to read the data recorded on the data band. After such recording or playback, the magnetic tape is usually stored wound on a reel inside a magnetic tape cartridge or the like until the next recording and / or playback is performed.
[0005] In order to improve the accuracy with which the magnetic head follows the data band of the magnetic tape during the above-mentioned recording and / or reproduction, a system (hereinafter, referred to as a "servo system") that performs head tracking using a servo signal has been put into practical use. However, when recording and / or reproduction is performed after the above-mentioned storage, a phenomenon (generally called "off-track") may occur in which the magnetic head for recording and / or reproducing data is displaced from the target track position due to deformation of the tape width of the magnetic tape caused by storage. If the off-track causes overwriting of recorded data, playback failure, etc., the operational stability of the drive is reduced. In recent years, the high density of the track density associated with the high capacity of magnetic tape has made it easier for off-track to occur, and therefore there is an increasing need to improve the operational stability of the drive. On the other hand, in recent years, in the data storage field, long-term storage of data, known as an archive, has been carried out. However, generally, the longer the storage period, the easier it is for the magnetic tape to deform in tape width, and the frequency of off-track occurrence tends to increase.
[0006] In view of the above, an object of one aspect of the present invention is to provide a magnetic tape that can contribute to improving the operational stability of a drive during recording and / or playback after long-term storage. [Means for solving the problem]
[0007] One aspect of the present invention is as follows. [1] A magnetic tape having a non-magnetic support and a magnetic layer containing ferromagnetic powder, The Sci measured on the surface of the magnetic layer using an atomic force microscope and calculated by the following formula A (hereinafter also referred to as "Sci of the magnetic layer surface" or simply "Sci") is 1.40 or more and 1.60 or less, and A magnetic tape in which the standard deviation σ of Sci in the width direction of the surface of the magnetic layer (hereinafter also referred to as "width direction σ of Sci") is 0.05 or less.
number
[10] The magnetic tape according to any one of [1] to [9], wherein the tape thickness is 5.0 μm or less.
[11] The magnetic tape according to any one of [1] to
[10] , wherein the magnetic tape has a squareness ratio in the perpendicular direction of 0.60 or more.
[12] The magnetic tape according to any one of [1] to
[11] , wherein the magnetic tape has a squareness ratio in the perpendicular direction of 0.65 or more.
[13] The magnetic tape according to any one of [1] to
[12] , wherein the non-magnetic support is an aromatic polyamide support.
[14] The standard deviation σ of the above Sci is less than or equal to 0.04. a non-magnetic layer containing a non-magnetic powder between the non-magnetic support and the magnetic layer, The non-magnetic powder of the non-magnetic layer has an average particle volume of 2.0×10 -6 μm 3 The present invention includes the following Fe-based inorganic oxide powder and carbon black having a pH of 9.0 or less: the thickness of the nonmagnetic layer is 0.1 μm or more and 0.7 μm or less, the non-magnetic support further comprises a backcoat layer containing a non-magnetic powder on the surface side opposite to the surface side having the magnetic layer, The non-magnetic powder of the backcoat layer includes non-magnetic powder having an average plate diameter of 50 nm or more and 1000 nm or less and an average plate thickness of 12 nm or less, The tape thickness is 5.0 μm or less, and The magnetic tape according to any one of [1] to
[13] , wherein the magnetic tape has a squareness ratio in the perpendicular direction of 0.65 or more.
[15] A magnetic tape cartridge comprising the magnetic tape according to any one of [1] to
[14] .
[16] A magnetic tape device including the magnetic tape described in any one of [1] to
[14] .
[17] Further comprising a magnetic head, The magnetic head has a module including an element array having a plurality of magnetic head elements between a pair of servo signal read elements; and The magnetic tape device according to
[16] , wherein the angle θ that the axis of the element array makes with respect to the width direction of the magnetic tape is changed while the magnetic tape is running within the magnetic tape device. Effect of the Invention
[0008] According to one aspect of the present invention, it is possible to provide a magnetic tape that contributes to improving the operational stability of a drive during recording and / or playback after long-term storage. Also, according to one aspect of the present invention, it is possible to provide a magnetic tape cartridge and a magnetic tape device including such a magnetic tape. [Brief description of the drawings]
[0009] [Figure 1] 1 shows an example of a track profile in which the horizontal axis represents the track position and the vertical axis represents the output of the reproduced signal. [Diagram 2] 1 shows an example of a graph relating to an initial nonlinear component. [Diagram 3] 13 shows an example of a graph regarding the nonlinear component after storage. [Figure 4] 13 is an example of a graph showing the absolute value of the difference between the initial nonlinear component and the nonlinear component after storage for each reproducing element (the difference between the nonlinear components before and after storage). [Diagram 5] FIG. 2 is a schematic diagram showing an example of a magnetic head module. [Figure 6] 2 is an explanatory diagram of the relative positional relationship between a module and a magnetic tape while the magnetic tape is running in a magnetic tape device; FIG. [Figure 7] FIG. 11 is an explanatory diagram regarding a change in angle θ while a magnetic tape is running. [Figure 8] 1 shows an example of a manufacturing process for a magnetic tape (schematic diagram of the process). [Figure 9] 2 shows an example of the arrangement of data bands and servo bands. [Figure 10] An example of servo pattern arrangement on an LTO (Linear Tape-Open) Ultrium format tape is shown. [Figure 11] FIG. 4 is an explanatory diagram of a method for measuring an angle θ during a magnetic tape run. [Figure 12] FIG. 1 is a schematic diagram illustrating an example of a magnetic tape device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Magnetic tape] One aspect of the present invention relates to a magnetic tape having a non-magnetic support and a magnetic layer containing a ferromagnetic powder, wherein Sci measured on the surface of the magnetic layer by an atomic force microscope and calculated by the above formula A is 1.40 to 1.60, and the standard deviation σ of Sci in the width direction of the surface of the magnetic layer is 0.05 or less.
[0011] As a result of intensive research, the present inventors have newly discovered that a magnetic tape in which the Sci of the magnetic layer surface is within the above range and the Sci width direction σ is within the above range can contribute to improving the operational stability of a drive. The present inventors' speculations on this point are described below. However, the present invention is not limited to the speculations described in this specification. As described above, the deformation of the tape width caused by long-term storage may cause a decrease in the operational stability of the magnetic tape in the drive. In this regard, in recent years, it has been proposed to obtain dimensional information of the magnetic tape in the width direction while the magnetic tape is running by using a servo signal, and to change the angle at which the axial direction of the magnetic head module is tilted with respect to the width direction of the magnetic tape (hereinafter, also referred to as the "head tilt angle") according to the obtained dimensional information (Patent Documents 1 and 2, for example, see paragraphs 0059 to 0067 and 0084 of Patent Document 1). In addition, it has also been practiced to obtain dimensional information of the magnetic tape in the width direction while the magnetic tape is running by using a servo signal, and to control the dimension of the magnetic tape in the width direction by adjusting the tension applied in the longitudinal direction of the magnetic tape according to the obtained dimensional information (for one example, see paragraph 0171 of Patent Document 3). For example, the above-mentioned dynamic track position control means while the magnetic tape is running can be a means for suppressing off-track. However, the present inventors, while conducting intensive research to further improve the operational stability of the drive in recording and / or playback after long-term storage, have noticed that there may be off-track factors that are difficult to compensate for by dynamic track position control means. This point will be further explained below. When the dynamic track position is controlled by changing the head tilt angle, the pitch of the magnetic head element (specifically, the recording element and / or the reproducing element) changes uniformly according to the head tilt angle, regardless of the position in the tape width direction. When the dynamic track position is controlled by adjusting the tension applied in the longitudinal direction of the magnetic tape, the tension is usually adjusted over the entire tape width, so that the tape width changes uniformly by tension adjustment, regardless of the position in the tape width direction. If the degree of tape width deformation is uniform over the entire magnetic tape, that is, if the tape width deformation component is only a linear component, it is possible to completely compensate for off-track by the control means. Therefore, it is possible to completely align the data track and the magnetic head element. On the other hand, if the degree of tape width deformation is different and non-uniform depending on the position, that is, if the tape width deformation component contains a non-linear component, it is difficult for the control means to compensate for off-track caused by the non-linear component. The inventors considered that reducing this non-linear component could contribute to suppressing the deterioration of the operation stability of the drive caused by the off-track factor, which is difficult to compensate for by the dynamic track position control means. In this regard, the present inventor believes that in a magnetic tape, the Sci of the magnetic layer surface and the standard deviation σ of Sci in the above range can contribute to suppressing the occurrence of the nonlinear component of the tape width deformation. As a result, the present inventor speculates that the magnetic tape can contribute to improving the operational stability of a drive during recording and / or playback after long-term storage.
[0012] <Sci of the magnetic layer surface and σ in the width direction of Sci> In the present invention and this specification, Sci (Core Fluid Retention Index) is determined by the following formula A, measured on the surface of the magnetic layer using an atomic force microscope (AFM).
[0013]
number
[0014] In formula A, Sq is the root mean square height Sq as defined in ISO 25178. Vv(h 0.05 )-Vv(h 0.8 ) is the void volume of the area on the bearing curve where the areal load factor is 5% or more and 80% or less. A is the area of the measurement area. ISO 25178 is an ISO standard for three-dimensional surface texture parameters, and is more specifically ISO 25178-2:2021 (Geometrical product specifications (GPS)-Surface texture:Areal-Part 2:Terms, definitions and surface texture parameters). Sci is a unitless value. To calculate Sci using formula A, for example, if "Sq" is expressed as a value in units of nm, "Vv(h 0.05 )-Vv(h 0.8 )" is in nm 3 The value of "A" is expressed in nm. 2 If you want to display "Sq" in units of μm, you can use "Vv(h 0.05 )-Vv(h 0.8 )" is in μm 3 The value of "A" is expressed in μm. 2 The value is displayed as
[0015] To determine the Sci of the magnetic layer surface, measurements are made on the surface of the magnetic layer of the magnetic tape using an atomic force microscope (AFM) as follows. In the present invention and this specification, the "surface of the magnetic layer" is synonymous with the surface of the magnetic tape on the magnetic layer side. The measurement area is a 40 μm square (40 μm × 40 μm). Therefore, the measurement area A in formula A is expressed in units of μm 2 If expressed as 1600μm 2The measurement is performed at five locations. The five locations for measuring the magnetic layer surface are five locations that are the same in the longitudinal direction but different in the width direction. The longitudinal positions are randomly selected on the magnetic layer surface, and the width direction is divided into five sections with respect to the magnetic tape width at these longitudinal positions (therefore, if the magnetic tape width is W, the width of each section is "W / 5"), and the Sci defined in ISO 25178 is obtained for a 40 μm square (40 μm x 40 μm) area randomly selected in each section. The Sci can be calculated using known AFM data analysis software. An example of the AFM data analysis software is the AFM data analysis software (Nanoscope Analysis) provided by BRUKER. The arithmetic average of the five measured values thus obtained is the Sci of the magnetic layer surface of the magnetic tape being measured. The standard deviation σ (ie, the positive square root of the variance) of the five measured values thus obtained is defined as the standard deviation σ of Sci in the width direction of the surface of the magnetic layer of the magnetic tape being measured (width direction σ of Sci). As an example of the AFM measurement conditions, the following measurement conditions can be mentioned. An AFM (BRUKER Nanoscope 5) is used in peak force tapping mode to measure an area of 40 μm × 40 μm on the surface of the magnetic layer of the magnetic tape. A BRUKER SCANASYST-AIR probe is used, with a resolution of 512 pixels × 512 pixels and a scan speed of 512 seconds per screen (512 pixels × 512 pixels).
[0016] (Sci of the magnetic layer surface) The Sci of the surface of the magnetic layer of the magnetic tape is 1.40 or more and 1.60 or less. From the viewpoint of improving the operational stability of the drive in recording and / or reproduction after long-term storage, the Sci of the magnetic layer surface is 1.40 or more, and preferably 1.45 or more. From the above viewpoint, the Sci of the magnetic layer surface is 1.60 or less, preferably 1.55 or less, and more preferably 1.50 or less.
[0017] (Sci width direction σ) The standard deviation σ of Sci in the width direction of the surface of the magnetic layer of the magnetic tape (width direction σ of Sci) is 0.05 or less, preferably 0.04 or less, from the viewpoint of improving the operational stability of the drive in recording and / or playback after long-term storage. The width direction σ of Sci can be, for example, 0.00 or more, 0.01 or more, or 0.02 or more. From the viewpoint of improving the operational stability of the drive in recording and / or playback after long-term storage, it is presumed that the smaller the value of the width direction σ of Sci, the more preferable it is.
[0018] A method for controlling Sci on the magnetic layer surface and a method for controlling the width direction σ of Sci will be described later.
[0019] <Nonlinear component of tape width deformation> The inventor believes that the "nonlinear component in the tape width direction caused by 10 days of storage in an environment with a temperature of 60°C and a relative humidity of 20%" obtained by the following method can be an indicator of the nonlinear component of the tape width deformation described above. Note that the storage condition of "10 days of storage in an environment with a temperature of 60°C and a relative humidity of 20%" is adopted as an example of storage conditions in an accelerated environment equivalent to long-term data storage called an archive, and the magnetic tape is not limited to those stored under such storage conditions. Unless otherwise specified, the following operations and measurements are carried out in an environment with a temperature of 20 to 25° C. and a relative humidity of 40 to 60%. The magnetic tape to be measured must be 200m or longer. The magnetic tape to be measured is wound onto a magnetic tape reel with a hub diameter (outer diameter, the same applies below) of 44 mm, with a tension of 0.6 N (Newton) applied to the magnetic tape in the longitudinal direction by a device having a winding mechanism that winds the magnetic tape by applying tension to the magnetic tape in the longitudinal direction. The magnetic tape thus wound onto the reel is stored for 24 hours or more in an environment with a temperature of 20 to 25°C and a relative humidity of 40 to 60% before the following measurement. Regarding one end and the other end of the magnetic tape, the end at the start point of winding onto the reel is called the inner end of the tape, and the other end is called the outer end of the tape. The following measurements are performed in the area within 100 m from the outer end of the tape (hereinafter referred to as the "outer tape area") and in the area within 100 m from the inner end of the tape (hereinafter referred to as the "inner tape area"), at the center wrap of each data band. The following measurements are performed using a magnetic head equipped with a reproducing module including an element array having 10 or more channels of reproducing elements with an element width (specifically, reproducing element width) of 0.2 μm to 1.0 μm between a pair of servo signal reading elements, and a recording module including an element array having 10 or more channels of recording elements with an element width (specifically, recording element width) of 1.2 μm to 2.9 μm between a pair of servo signal reading elements. The "element width" is the physical dimension of the element width, and can be measured by an optical microscope, a scanning electron microscope, or the like. In the recording module, the distance between two adjacent recording elements in the head width direction is 83.25 μm. In the reproducing module, the distance between two adjacent reproducing elements in the head width direction is 83.25 μm. The above distance is the distance between the centers of two adjacent recording elements in the recording module, and is the distance between the centers of two adjacent reproducing elements in the reproducing module, and can be measured by an optical microscope, or the like. In measurements for the examples and comparative examples described below, a magnetic head was used that included a recording module including an element array having 32 channels (channel 0 to channel 31) of recording elements between a pair of servo signal reading elements, and a reproduction module including an element array having 32 channels (channel 0 to channel 31) of reproduction elements between a pair of servo signal reading elements. The reel on which the magnetic tape to be measured is wound and the magnetic head are attached to the tape transport system of the magnetic tape device to record and reproduce data. The tape transport system is attached to a recording and reproducing amplifier capable of driving the magnetic head elements (more specifically, the recording element and the reproducing element) of the magnetic head. The recording and reproducing amplifier can be controlled from a computer (PC: Personal Computer) via a controller. The magnetic head is attached to an actuator (piezo motor or VCM (voice coil motor)) that operates in the tape width direction, and can perform servo following so that the magnetic head is at a constant track position while the tape is running based on the servo signal of the magnetic tape. In addition, in order to compensate for the linear component of the tape width deformation, the head tilt angle of the magnetic head can be changed to perform dynamic track position control so that the difference between the widthwise read positions PES (Position Error Signal) (PES1, PES2) based on the servo signals obtained by the two upper and lower servo signal reading elements is constant. The above servo following and dynamic track position control are performed during the following recording and reproduction. Next, while running the magnetic tape at a constant speed of 3.0 m / sec, for three consecutive wraps in the same running direction, a DC (Direct Current) pattern is recorded on the first wrap, a single frequency signal of 255 kfci is recorded on the second wrap, and a DC pattern is recorded on the third wrap. The unit "kfci" is a unit of linear recording density (cannot be converted to SI units). Shingle recording is performed on three or more tracks so that the difference between (PES1+PES2) / 2 is 1200 nm. Shingle recording is also called shingled recording. Next, data is reproduced over a length of 90 m from the central wrap of three consecutive wraps in an area within 100 m from the outer edge of the tape (outer tape area) and an area within 100 m from the inner edge of the tape (inner tape area). The reproduced signal waveform and servo signal waveform are acquired and stored using an oscilloscope. For each measurement, the track position of the reproducing element is moved in the tape width direction at intervals of 1 / 30 or less of the track pitch. The "reproduced signal output" is calculated for each reproducing element from the reproduced signal waveform acquired and stored using the oscilloscope, and the track position is calculated from the servo signal waveform. From these results, a track profile is created with the track position plotted on the horizontal axis and the reproduced signal output plotted on the vertical axis. Figure 1 shows an example of a track profile created in this way. The median between two track positions that are 1 dB or more lower than the maximum output of the reproduction signal is found, and the median is plotted on the vertical axis for each reproduction element, and a linear approximation line is obtained by linear fitting using the least squares method. For each reproduction element in the outer and inner tape regions, the difference between the linear approximation line and the actual measurement value is found, and this is defined as the "initial nonlinear component." Figure 2 shows an example of a graph related to the initial nonlinear component. In the example shown in Figure 2 and the example shown in Figure 3 described below, the number of reproduction elements (number of channels) is 32 channels (reproduction element numbers (No.): channel 0 to channel 31). After measuring the initial nonlinear component, the magnetic tape to be measured is wound onto a magnetic tape reel with a hub diameter of 44 mm, with a tension of 0.6 N applied to the magnetic tape in the longitudinal direction by a device having a winding mechanism that applies tension to the magnetic tape in the longitudinal direction. During this winding, the magnetic tape is wound so that the end that was the inner end of the tape when wound onto the reel before the measurement of the initial nonlinear component becomes the inner end of the tape. The magnetic tape thus wound onto the reel is stored in an environment with a temperature of 60°C and a relative humidity of 20% for 10 days. After the above storage, the magnetic tape to be measured is stored in an environment with a temperature of 20 to 25°C and a relative humidity of 40 to 60% for 24 hours or more (but up to 120 hours at the maximum) while still wound on the reel, and then the magnetic tape device used for measuring the initial nonlinear components is used to run the magnetic tape to be measured back and forth once (in the forward and reverse directions). Using the same recording element, reproducing element, magnetic tape device, and reproducing conditions as those used for measuring the initial nonlinear components, data is reproduced over a length of 90 m in an area within 100 m from the outer edge of the tape (outer tape area) and an area within 100 m from the inner edge of the tape (inner tape area). The output of the reproduced signal and the servo signal waveform are obtained and stored using the same oscilloscope as used for measuring the initial nonlinear components. The track position of the reproducing element is moved in the tape width direction for each measurement at the same intervals as those used for measuring the initial nonlinear components. The "output of the reproduced signal" is calculated for each reproducing element from the reproduced signal waveforms obtained and stored using the oscilloscope, and the track position is calculated from the servo signal waveforms. From these results, a track profile is created by plotting the track position on the horizontal axis and the playback signal output on the vertical axis. Figure 1 is an example of a track profile created in this way. The median value between two track positions where the playback signal output is 1 dB or more lower than the maximum value is found, and the median value is plotted on the vertical axis for each playback element, and a linear approximation line is obtained by linear fitting using the least squares method. The difference between the linear approximation line and the actual measured value is found for each playback element for both the outer and inner tape regions, and this is defined as the "nonlinear component after storage." Figure 3 shows an example of a graph related to the nonlinear component after storage. The absolute value of the difference between the "initial nonlinear component" and the "nonlinear component after storage" for each reproducing element (the difference in the nonlinear component before and after storage) is calculated. Figure 4 shows an example of a graph showing the absolute value of the difference thus calculated for each reproducing element. The maximum value of the absolute value in the outer tape area and the inner tape area is taken as the "nonlinear component of tape width deformation" of the magnetic tape being measured. It is believed that the initial nonlinear component can be said to be a nonlinear component caused by factors other than the magnetic tape. Therefore, the inventor believes that by calculating the difference in the nonlinear component before and after storage as described above, it is possible to accurately evaluate the nonlinear component caused by the magnetic tape.
[0020] The nonlinear component of the tape width deformation obtained by the method described above for the magnetic tape is preferably 100 nm or less, more preferably 95 nm or less, and more preferably 90 nm or less, 85 nm or less, 80 nm or less, 75 nm or less, 70 nm or less, 65 nm or less, 60 nm or less, 55 nm or less, and 50 nm or less in this order, from the viewpoint of improving the operation stability of the drive in recording and / or playback after long-term storage. The Sci and width direction σ of Sci on the magnetic layer surface being in the above range can contribute to controlling the value of the nonlinear component within the above range. In addition, the nonlinear component of the tape width deformation can be, for example, 0 nm or more, more than 0 nm, 1 nm or more, 5 nm or more, 10 nm or more, 15 nm or more, 20 nm or more, 25 nm or more, 30 nm or more, 35 nm or more, or 40 nm or more. From the viewpoint of improving the operation stability of the drive, the smaller the nonlinear component of the tape width deformation, the more preferable it is.
[0021] <Explanation of head tilt angle> As described above, one example of a means for controlling the dynamic track position while the magnetic tape is running is to change the head tilt angle. In this regard, the configuration of the magnetic head, the head tilt angle, etc. will be described below. Furthermore, the reason why it is possible to control the dynamic track position while the magnetic tape is running by tilting the axial direction of the magnetic head module relative to the width direction of the magnetic tape while the magnetic tape is running will be described below.
[0022] The magnetic head may have one or more modules, two or more modules, or three or more modules, each module including an element array having a plurality of magnetic head elements between a pair of servo signal reading elements. The total number of such modules may be, for example, five or less, four or less, or three or less, or the magnetic head may include a number of modules exceeding the total number exemplified here. Examples of the arrangement of a plurality of modules include "recording module-playback module" (total number of modules: 2), "recording module-playback module-recording module" (total number of modules: 3), etc. However, the arrangement is not limited to the examples shown here.
[0023] Each module may include an element array having a plurality of magnetic head elements between a pair of servo signal reading elements, i.e., an array of elements. A module having a recording element as a magnetic head element is a recording module for recording data onto a magnetic tape. A module having a reproducing element as a magnetic head element is a reproducing module for reproducing data recorded onto a magnetic tape. In a magnetic head, a plurality of modules are arranged, for example, in a recording / reproducing head unit, with the axes of the element arrays of the respective modules oriented in parallel. Such "parallel" does not necessarily mean only parallel in the strict sense, but includes the range of error normally permitted in the technical field to which the present invention belongs. The range of error may mean, for example, a range of strict parallelism ±10° or less.
[0024] In each element array, a pair of servo signal read elements and a plurality of magnetic head elements (i.e., recording elements or reproducing elements) are usually arranged in a line, spaced apart from each other. Here, "arranged in a line" means that each magnetic head element is arranged on a line connecting the center of one servo signal read element and the center of the other servo signal read element. In this invention and this specification, the "axis of the element array" means the line connecting the center of one servo signal read element and the center of the other servo signal read element.
[0025] Next, the configuration of the module will be further described with reference to the drawings. However, the embodiments shown in the drawings are merely examples and do not limit the present invention.
[0026] FIG. 5 is a schematic diagram showing an example of a magnetic head module. The module shown in FIG. 5 has multiple magnetic head elements between a pair of servo signal reading elements (servo signal reading elements 1 and 2). The magnetic head elements are also called "channels." "Ch" in the figure is an abbreviation for Channel. The module shown in FIG. 5 has a total of 32 magnetic head elements, Ch0 to Ch31.
[0027] In Fig. 5, "L" is the distance between a pair of servo signal read elements, i.e., the distance between one servo signal read element and the other servo signal read element. In the module shown in Fig. 5, "L" is the distance between servo signal read element 1 and servo signal read element 2. More specifically, it is the distance between the center of servo signal read element 1 and the center of servo signal read element 2. Such a distance can be measured, for example, by an optical microscope.
[0028] FIG. 6 is an explanatory diagram of the relative positional relationship between a module and a magnetic tape in a magnetic tape device while the magnetic tape is running. In FIG. 6, dotted line A indicates the width direction of the magnetic tape. Dotted line B indicates the axis of the element array. Angle θ can be said to be the head tilt angle while the magnetic tape is running, and is the angle formed by dotted lines A and B. When angle θ is 0° while the magnetic tape is running, the distance in the magnetic tape width direction between one servo signal reading element and the other servo signal reading element of the element array (hereinafter also referred to as "effective distance between servo signal reading elements") is "L". In contrast, when angle θ is greater than 0°, the effective distance between servo signal reading elements is "Lcosθ", and Lcosθ is smaller than L. In other words, "Lcosθ" <L」である。
[0029] As described above, when recording or reproducing, if the magnetic head for recording or reproducing data deviates from the target track position due to the deformation of the magnetic tape, phenomena such as overwriting of recorded data and reproduction failure may occur. For example, when the width of the magnetic tape shrinks or expands, a phenomenon may occur in which the magnetic head element that should record or reproduce at the target track position records or reproduces at a different track position. In addition, when the width of the magnetic tape expands, the effective distance between the servo signal reading elements becomes shorter than the distance between two adjacent servo bands sandwiching the data band (also referred to as the "servo band distance" or "servo band distance". More specifically, the distance between the two servo bands in the width direction of the magnetic tape.), and a phenomenon may occur in which data is not recorded or reproduced near the edge of the magnetic tape. In contrast, when the element array is tilted at an angle θ exceeding 0°, the effective distance between the servo signal reading elements is “Lcosθ” as described above. The larger the value of θ, the smaller the value of Lcosθ, and the smaller the value of θ, the larger the value of Lcosθ. Therefore, by changing the value of θ according to the degree of dimensional change in the width direction of the magnetic tape (i.e., contraction or expansion), it is possible to make the effective distance between the servo signal reading elements approach or match the interval of the servo band. This makes it possible to prevent or reduce the frequency of occurrence of phenomena such as overwriting of recorded data and playback failure caused by the magnetic head for recording or playing back data being shifted from the target track position due to the width deformation of the magnetic tape during recording or playback.
[0030] FIG. 7 is an explanatory diagram regarding the change in angle θ during the running of the magnetic tape. θ is the angle θ at the start of travel. initial can be set, for example, to be equal to or greater than 0°. The central diagram in Figure 7 shows the state of the module at the start of driving. In Figure 7, the right diagram shows the angle θ as θ initial The larger angle, angle θ cThe effective distance between the servo signal reading elements Lcosθ is shown. c is Lcosθ when the magnetic tape starts running initial It is preferable to perform such an angle adjustment when the width of the magnetic tape contracts during its running. On the other hand, in the left diagram of FIG. 7, the angle θ is initial The smaller angle, θ e The effective distance between the servo signal reading elements Lcosθ is shown. e is Lcosθ when the magnetic tape starts running initial It is preferable to perform such an angle adjustment when the width of the magnetic tape expands during its running.
[0031] As described above, changing the head tilt angle while the magnetic tape is running can help prevent phenomena such as overwriting of recorded data and playback failures that occur when the magnetic head for recording or reproducing data deviates from the target track position due to deformation of the magnetic tape during recording or reproduction, or can help reduce the frequency of such occurrences. However, for example, in the dynamic track position control means as described above, while it is usually possible to compensate for off-track caused by the linear component of the tape width deformation, it is difficult to suppress off-track caused by the nonlinear component. In contrast, in the magnetic tape, it is presumed that the Sci and width direction σ of Sci on the magnetic layer surface in the above range contribute to reducing the nonlinear component of the tape width deformation. It is considered that this makes it possible to improve the operating stability of the drive. Such a magnetic tape is preferable for increasing the track density.
[0032] The above magnetic tape will now be described in more detail.
[0033] <Magnetic layer> (Ferromagnetic powder) As the ferromagnetic powder contained in the magnetic layer, one or more of the ferromagnetic powders known as ferromagnetic powders used in the magnetic layers of various magnetic recording media can be used in combination. It is preferable to use ferromagnetic powders with a small average particle size from the viewpoint of improving recording density. From this viewpoint, the average particle size of the ferromagnetic powder is preferably 50 nm or less, more preferably 45 nm or less, even more preferably 40 nm or less, even more preferably 35 nm or less, even more preferably 30 nm or less, even more preferably 25 nm or less, and even more preferably 20 nm or less. On the other hand, from the viewpoint of magnetization stability, the average particle size of the ferromagnetic powder is preferably 5 nm or more, more preferably 8 nm or more, even more preferably 10 nm or more, even more preferably 15 nm or more, and even more preferably 20 nm or more.
[0034] Hexagonal Ferrite Powder A preferred specific example of the ferromagnetic powder is hexagonal ferrite powder. For details of the hexagonal ferrite powder, see, for example, JP2011-225417A, paragraphs 0012-0030, JP2011-216149A, paragraphs 0134-0136, JP2012-204726A, paragraphs 0013-0030, and JP2015-127985A, paragraphs 0029-0084.
[0035] In the present invention and this specification, the term "hexagonal ferrite powder" refers to a ferromagnetic powder in which the crystal structure of hexagonal ferrite is detected as the main phase by X-ray diffraction analysis. The main phase refers to the structure to which the diffraction peak with the highest intensity is assigned in the X-ray diffraction spectrum obtained by X-ray diffraction analysis. For example, when the diffraction peak with the highest intensity in the X-ray diffraction spectrum obtained by X-ray diffraction analysis is assigned to the crystal structure of hexagonal ferrite, it is determined that the crystal structure of hexagonal ferrite is detected as the main phase. When only a single structure is detected by X-ray diffraction analysis, the detected structure is regarded as the main phase. The crystal structure of hexagonal ferrite contains at least an iron atom, a divalent metal atom, and an oxygen atom as constituent atoms. The divalent metal atom is a metal atom that can become a divalent cation as an ion, and examples of the divalent metal atom include an alkaline earth metal atom such as a strontium atom, a barium atom, and a calcium atom, and a lead atom. In the present invention and this specification, the hexagonal strontium ferrite powder refers to a powder in which the main divalent metal atom contained therein is a strontium atom, and the hexagonal barium ferrite powder refers to a powder in which the main divalent metal atom contained therein is a barium atom. The main divalent metal atom refers to the divalent metal atom that is the most abundant of the divalent metal atoms contained in the powder on an atomic % basis. However, the above divalent metal atoms do not include rare earth atoms. In the present invention and this specification, the "rare earth atom" is selected from the group consisting of scandium atoms (Sc), yttrium atoms (Y), and lanthanoid atoms. The lanthanide atom is selected from the group consisting of a lanthanum atom (La), a cerium atom (Ce), a praseodymium atom (Pr), a neodymium atom (Nd), a promethium atom (Pm), a samarium atom (Sm), a europium atom (Eu), a gadolinium atom (Gd), a terbium atom (Tb), a dysprosium atom (Dy), a holmium atom (Ho), an erbium atom (Er), a thulium atom (Tm), a ytterbium atom (Yb), and a lutetium atom (Lu).
[0036] Hereinafter, hexagonal strontium ferrite powder, which is one form of hexagonal ferrite powder, will be described in more detail.
[0037] The activation volume of the hexagonal strontium ferrite powder is preferably 800 to 1600 nm 3 The finely divided hexagonal strontium ferrite powder having an activation volume in the above range is suitable for producing a magnetic tape exhibiting excellent electromagnetic conversion characteristics. The activation volume of the hexagonal strontium ferrite powder is preferably 800 nm 3 For example, 850 nm or more. 3 From the viewpoint of further improving the electromagnetic conversion characteristics, the activation volume of the hexagonal strontium ferrite powder can be 1500 nm or more. 3 More preferably, it is 1400 nm or less. 3 More preferably, it is 1300 nm or less. 3 More preferably, it is 1200 nm or less. 3 More preferably, it is equal to or less than 1100 nm. 3 It is even more preferable that the activation volume of the hexagonal barium ferrite powder is equal to or less than 1000 nm. The same is true for the activation volume of the hexagonal barium ferrite powder.
[0038] "Activation volume" is a unit of magnetization reversal and is an index showing the magnetic size of a particle. The activation volume and the anisotropy constant Ku described in the present invention and this specification are values obtained by measuring the coercive force Hc measurement section at magnetic field sweep speeds of 3 minutes and 30 minutes (measurement temperature: 23°C ± 1°C) using a vibrating sample magnetometer, and calculating from the following relationship between Hc and activation volume V. The unit of the anisotropy constant Ku is 1 erg / cc = 1.0 x 10 -1 J / m 3 It is. Hc=2Ku / Ms{1-[(kT / KuV)ln(At / 0.693)] 1 / 2} [In the above formula, Ku: anisotropy constant (unit: J / m 3 ), Ms: saturation magnetization (unit: kA / m), k: Boltzmann constant, T: absolute temperature (unit: K), V: activation volume (unit: cm 3 ), A: spin precession frequency (unit: s -1 ), t: magnetic field reversal time (unit: s)]
[0039] The anisotropy constant Ku can be used as an index of reduction in thermal fluctuation, in other words, improvement in thermal stability. The hexagonal strontium ferrite powder is preferably 1.8×10 5 J / m 3 More preferably, the Ku is 2.0×10 or more. 5 J / m 3 The Ku of the hexagonal strontium ferrite powder can be, for example, 2.5×10 5 J / m 3 However, since a higher Ku value means higher thermal stability and is preferable, the Ku value is not limited to the above-mentioned values.
[0040] The hexagonal strontium ferrite powder may or may not contain rare earth atoms. When the hexagonal strontium ferrite powder contains rare earth atoms, it is preferable that the rare earth atoms are contained at a content (bulk content) of 0.5 to 5.0 atomic % relative to 100 atomic % of iron atoms. In one embodiment, the hexagonal strontium ferrite powder containing rare earth atoms can have uneven distribution of rare earth atoms in the surface layer portion. In the present invention and this specification, the term "surface distribution of rare earth atoms" refers to the rare earth atom content relative to 100 atomic % of iron atoms in a solution obtained by partially dissolving a hexagonal strontium ferrite powder in an acid (hereinafter referred to as "surface content of rare earth atoms" or simply "surface content" for rare earth atoms), which is greater than the rare earth atom content relative to 100 atomic % of iron atoms in a solution obtained by completely dissolving a hexagonal strontium ferrite powder in an acid (hereinafter referred to as "bulk content of rare earth atoms" or simply "bulk content" for rare earth atoms), Rare earth atom surface content / rare earth atom bulk content>1.0 The rare earth atom content of the hexagonal strontium ferrite powder described later is synonymous with the rare earth atom bulk content. In contrast, partial dissolution using an acid dissolves the surface layer of the particles constituting the hexagonal strontium ferrite powder, so the rare earth atom content in the solution obtained by partial dissolution is the rare earth atom content in the surface layer of the particles constituting the hexagonal strontium ferrite powder. The rare earth atom surface layer content satisfying the ratio of "rare earth atom surface layer content / rare earth atom bulk content>1.0" means that the rare earth atoms are unevenly distributed (i.e., more present in the surface layer) in the particles constituting the hexagonal strontium ferrite powder. In the present invention and this specification, the surface layer refers to a portion of the region extending from the surface of the particles constituting the hexagonal strontium ferrite powder toward the inside.
[0041] When the hexagonal strontium ferrite powder contains rare earth atoms, the rare earth atom content (bulk content) is preferably in the range of 0.5 to 5.0 atomic % relative to 100 atomic % of iron atoms. It is considered that the rare earth atoms contained in the bulk content in the above range and the rare earth atoms unevenly distributed in the surface layer of the particles constituting the hexagonal strontium ferrite powder contribute to suppressing the decrease in the reproduction output during repeated reproduction. This is presumed to be because the hexagonal strontium ferrite powder contains rare earth atoms in the bulk content in the above range and the rare earth atoms unevenly distributed in the surface layer of the particles constituting the hexagonal strontium ferrite powder can increase the anisotropy constant Ku. The higher the value of the anisotropy constant Ku, the more the occurrence of a phenomenon called thermal fluctuation can be suppressed (in other words, the thermal stability can be improved). By suppressing the occurrence of thermal fluctuation, the decrease in the reproduction output during repeated reproduction can be suppressed. It is speculated that the uneven distribution of rare earth atoms in the surface layer of hexagonal strontium ferrite powder particles contributes to stabilizing the spin of the iron (Fe) sites in the crystal lattice of the surface layer, thereby increasing the anisotropy constant Ku. In addition, it is presumed that using the hexagonal strontium ferrite powder having rare earth atom uneven distribution on the surface as the ferromagnetic powder of the magnetic layer also contributes to suppressing the wear of the magnetic layer surface due to sliding with the magnetic head. That is, it is presumed that the hexagonal strontium ferrite powder having rare earth atom uneven distribution on the surface can also contribute to improving the running durability of the magnetic tape. This is presumed to be because the uneven distribution of rare earth atoms on the surface of the particles constituting the hexagonal strontium ferrite powder contributes to improving the interaction between the particle surface and the organic substance (e.g., binder and / or additive) contained in the magnetic layer, and as a result, the strength of the magnetic layer is improved. From the viewpoint of further suppressing the decrease in regeneration output during repeated regeneration and / or further improving running durability, the rare earth atom content (bulk content) is more preferably in the range of 0.5 to 4.5 atomic %, even more preferably in the range of 1.0 to 4.5 atomic %, and even more preferably in the range of 1.5 to 4.5 atomic %.
[0042] The bulk content is the content obtained by completely dissolving the hexagonal strontium ferrite powder. In the present invention and this specification, unless otherwise specified, the content of an atom refers to the bulk content obtained by completely dissolving the hexagonal strontium ferrite powder. The hexagonal strontium ferrite powder containing rare earth atoms may contain only one rare earth atom as a rare earth atom, or may contain two or more rare earth atoms. When two or more rare earth atoms are contained, the bulk content is obtained for the total of two or more rare earth atoms. This point is the same for other components in the present invention and this specification. That is, unless otherwise specified, a certain component may be used in only one type, or in two or more types. When two or more types are used, the content or content refers to the total of two or more types.
[0043] When the hexagonal strontium ferrite powder contains rare earth atoms, the rare earth atoms contained therein may be any one or more of rare earth atoms. From the viewpoint of further suppressing the decrease in the reproduction output during repeated reproduction, preferred rare earth atoms include neodymium atoms, samarium atoms, yttrium atoms and dysprosium atoms, more preferred are neodymium atoms, samarium atoms and yttrium atoms, and even more preferred are neodymium atoms.
[0044] In the hexagonal strontium ferrite powder having rare earth atom uneven distribution in the surface layer, the rare earth atoms may be unevenly distributed in the surface layer of the particles constituting the hexagonal strontium ferrite powder, and the degree of uneven distribution is not limited. For example, for the hexagonal strontium ferrite powder having rare earth atom uneven distribution in the surface layer, the ratio of the surface content of rare earth atoms obtained by partial dissolution under the dissolution conditions described below to the bulk content of rare earth atoms obtained by complete dissolution under the dissolution conditions described below, "surface content / bulk content", is more than 1.0 and can be 1.5 or more. The "surface content / bulk content" being greater than 1.0 means that the rare earth atoms are unevenly distributed in the surface layer (i.e., more than in the interior) in the particles constituting the hexagonal strontium ferrite powder. In addition, the ratio of the surface layer content of rare earth atoms obtained by partial dissolution under the dissolution conditions described later to the bulk content of rare earth atoms obtained by total dissolution under the dissolution conditions described later, "surface layer content / bulk content", can be, for example, 10.0 or less, 9.0 or less, 8.0 or less, 7.0 or less, 6.0 or less, 5.0 or less, or 4.0 or less. However, in a hexagonal strontium ferrite powder having rare earth atom surface layer uneven distribution, it is sufficient that the rare earth atoms are unevenly distributed in the surface layer of the particles constituting the hexagonal strontium ferrite powder, and the above "surface layer content / bulk content" is not limited to the upper or lower limit exemplified.
[0045] The partial and total dissolution of hexagonal strontium ferrite powder will be described below. For hexagonal strontium ferrite powder present as powder, the sample powders to be partially and completely dissolved are taken from the same lot of powder. On the other hand, for hexagonal strontium ferrite powder contained in the magnetic layer of a magnetic tape, a part of the hexagonal strontium ferrite powder taken out from the magnetic layer is subjected to partial dissolution, and the other part is subjected to total dissolution. The hexagonal strontium ferrite powder can be taken out from the magnetic layer by, for example, the method described in paragraph 0032 of JP 2015-91747 A. The above-mentioned partial dissolution means that the hexagonal strontium ferrite powder is dissolved to such an extent that the remaining powder can be visually confirmed in the liquid at the end of dissolution. For example, the partial dissolution can dissolve a region of 10 to 20 mass% of the particles constituting the hexagonal strontium ferrite powder, with the whole particles being 100 mass%. On the other hand, the above-mentioned complete dissolution means that the hexagonal strontium ferrite powder is dissolved to such an extent that the remaining powder cannot be visually confirmed in the liquid at the end of dissolution. The partial dissolution and the surface layer content are measured, for example, by the following method. Note that the dissolution conditions such as the amount of sample powder are merely examples, and any dissolution conditions that allow partial or complete dissolution can be used. A container (e.g., a beaker) containing 12 mg of sample powder and 10 mL of 1 mol / L hydrochloric acid is placed on a hot plate set at 70°C for 1 hour. The resulting solution is filtered through a 0.1 μm membrane filter. Elemental analysis of the filtrate thus obtained is performed using an inductively coupled plasma (ICP) analyzer. In this way, the surface layer content of rare earth atoms relative to 100 atomic % of iron atoms can be determined. When multiple types of rare earth atoms are detected by elemental analysis, the total content of all rare earth atoms is taken as the surface layer content. This is also true for the measurement of bulk content. On the other hand, the total dissolved and bulk contents are measured, for example, by the following method. A container (e.g., a beaker) containing 12 mg of sample powder and 10 mL of 4 mol / L hydrochloric acid is placed on a hot plate set at 80° C. for 3 hours. After that, the bulk content relative to 100 atomic % of iron atoms can be calculated by carrying out the same procedure as the partial dissolution and surface layer content measurement described above.
[0046] From the viewpoint of increasing the reproduction output when reproducing data recorded on a magnetic tape, it is desirable for the mass magnetization σs of the ferromagnetic powder contained in the magnetic tape to be high. In this regard, hexagonal strontium ferrite powder that contains rare earth atoms but does not have uneven distribution of rare earth atoms in the surface layer has a tendency to have a significantly lower σs than hexagonal strontium ferrite powder that does not contain rare earth atoms. In contrast, hexagonal strontium ferrite powder that has uneven distribution of rare earth atoms in the surface layer is considered to be preferable in terms of suppressing such a large decrease in σs. In one embodiment, the σs of the hexagonal strontium ferrite powder is 45 A·m 2 / kg or more, and 47A·m 2 / kg or more. On the other hand, from the viewpoint of noise reduction, σs is 80A·m 2 / kg or less, and 60A·m 2 / kg or less. σs can be measured using a known measuring device capable of measuring magnetic properties, such as a vibrating sample magnetometer. In the present invention and this specification, unless otherwise specified, the mass magnetization σs is a value measured at a magnetic field strength of 15 kOe. 1 [kOe]=10 6 / 4π[A / m].
[0047] Regarding the content (bulk content) of the constituent atoms of the hexagonal strontium ferrite powder, the strontium atom content can be, for example, in the range of 2.0 to 15.0 atomic % relative to 100 atomic % of iron atoms. In one embodiment, the divalent metal atoms contained in the hexagonal strontium ferrite powder can be only strontium atoms. In another embodiment, the hexagonal strontium ferrite powder can also contain one or more other divalent metal atoms in addition to strontium atoms. For example, it can contain barium atoms and / or calcium atoms. When divalent metal atoms other than strontium atoms are contained, the barium atom content and calcium atom content in the hexagonal strontium ferrite powder can each be, for example, in the range of 0.05 to 5.0 atomic % relative to 100 atomic % of iron atoms.
[0048] Known crystal structures of hexagonal ferrite include magnetoplumbite type (also called "M type"), W type, Y type, and Z type. The hexagonal strontium ferrite powder may have any of the crystal structures. The crystal structure can be confirmed by X-ray diffraction analysis. The hexagonal strontium ferrite powder may be one in which a single crystal structure or two or more types of crystal structures are detected by X-ray diffraction analysis. For example, in one embodiment, the hexagonal strontium ferrite powder may be one in which only the M-type crystal structure is detected by X-ray diffraction analysis. For example, M-type hexagonal ferrite is AFe 12 O 19Here, A represents a divalent metal atom, and when the hexagonal strontium ferrite powder is of the M type, A is only a strontium atom (Sr), or when A contains a plurality of divalent metal atoms, the strontium atom (Sr) accounts for the largest proportion on an atomic % basis as described above. The divalent metal atom content of the hexagonal strontium ferrite powder is usually determined by the type of crystal structure of the hexagonal ferrite, and is not particularly limited. The same applies to the iron atom content and the oxygen atom content. The hexagonal strontium ferrite powder contains at least an iron atom, a strontium atom, and an oxygen atom, and may further contain a rare earth atom. Furthermore, the hexagonal strontium ferrite powder may or may not contain atoms other than these atoms. As an example, the hexagonal strontium ferrite powder may contain an aluminum atom (Al). The content of aluminum atoms can be, for example, 0.5 to 10.0 atomic % relative to 100 atomic % of iron atoms. From the viewpoint of further suppressing the decrease in the reproduction output during repeated reproduction, the hexagonal strontium ferrite powder contains iron atoms, strontium atoms, oxygen atoms, and rare earth atoms, and the content of atoms other than these atoms is preferably 10.0 atomic % or less, more preferably in the range of 0 to 5.0 atomic %, relative to 100 atomic % of iron atoms, and may be 0 atomic %. That is, in one embodiment, the hexagonal strontium ferrite powder may not contain atoms other than iron atoms, strontium atoms, oxygen atoms, and rare earth atoms. The content expressed in atomic % above is obtained by converting the content (unit: mass %) of each atom obtained by completely dissolving the hexagonal strontium ferrite powder into a value expressed in atomic % using the atomic weight of each atom. In addition, in the present invention and this specification, "not containing" a certain atom means that the content measured by an ICP analyzer after completely dissolving is 0 mass %. The detection limit of an ICP analyzer is usually 0.01 ppm (parts per million) or less on a mass basis. The above term "free" is used to mean that the content is below the detection limit of the ICP analyzer.In one form, the hexagonal strontium ferrite powder can be one that does not contain bismuth atoms (Bi).
[0049] metal powder A specific preferred example of the ferromagnetic powder is a ferromagnetic metal powder. For details of the ferromagnetic metal powder, reference can be made to, for example, paragraphs 0137 to 0141 of JP 2011-216149 A and paragraphs 0009 to 0023 of JP 2005-251351 A.
[0050] ε-iron oxide powder A preferred specific example of the ferromagnetic powder is ε-iron oxide powder. In the present invention and this specification, the term "ε-iron oxide powder" refers to a ferromagnetic powder in which the ε-iron oxide crystal structure is detected as the main phase by X-ray diffraction analysis. For example, when the highest intensity diffraction peak in the X-ray diffraction spectrum obtained by X-ray diffraction analysis is assigned to the ε-iron oxide crystal structure, it is determined that the ε-iron oxide crystal structure is detected as the main phase. Known methods for producing ε-iron oxide powder include a method of producing it from goethite and a reverse micelle method. All of the above production methods are publicly known. In addition, for a method for producing ε-iron oxide powder in which a part of Fe is replaced by a substitution atom such as Ga, Co, Ti, Al, or Rh, reference can be made to, for example, J. Jpn. Soc. Powder Metallurgy Vol. 61 Supplement, No. S1, pp. S280-S284, J. Mater. Chem. C, 2013, 1, pp.5200-5206, etc. However, the method for producing the ε-iron oxide powder that can be used as the ferromagnetic powder in the magnetic layer of the magnetic tape is not limited to the method given here.
[0051] The activation volume of the ε-iron oxide powder is preferably 300 to 1500 nm 3 The finely divided ε-iron oxide powder exhibiting an activation volume in the above range is suitable for producing a magnetic tape exhibiting excellent electromagnetic conversion characteristics. The activation volume of the ε-iron oxide powder is preferably 300 nm 3 For example, 500 nm or more.3 From the viewpoint of further improving the electromagnetic conversion characteristics, the activation volume of the ε-iron oxide powder can be 1400 nm or more. 3 More preferably, it is 1300 nm or less. 3 More preferably, it is 1200 nm or less. 3 More preferably, it is equal to or less than 1100 nm. 3 It is even more preferred that:
[0052] The anisotropy constant Ku can be used as an index of the reduction in thermal fluctuation, in other words, the improvement in thermal stability. The ε-iron oxide powder is preferably 3.0×10 4 J / m 3 More preferably, the Ku is 8.0×10 or more. 4 J / m 3 The Ku of the ε-iron oxide powder can be, for example, 3.0×10 5 J / m 3 However, since a higher Ku value means higher thermal stability and is preferable, the Ku value is not limited to the above-mentioned values.
[0053] From the viewpoint of increasing the reproduction output when reproducing data recorded on a magnetic tape, it is desirable that the mass magnetization σs of the ferromagnetic powder contained in the magnetic tape is high. In this regard, in one embodiment, the σs of the ε-iron oxide powder is 8 A m 2 / kg or more, and 12 A m 2 On the other hand, the σs of ε-iron oxide powder is 40 A m 2 / kg or less, and 35A·m 2 It is more preferable that the amount is not more than 1 / kg.
[0054] In the present invention and this specification, unless otherwise specified, the average particle size of various powders such as ferromagnetic powders is a value measured by the following method using a transmission electron microscope. The powder is photographed at a magnification of 100,000 times using a transmission electron microscope, and the photograph is printed on photographic paper or displayed on a display so that the total magnification is 500,000 times to obtain a particle photograph of the particles that make up the powder. From the obtained particle photograph, the target particle is selected, and the particle outline is traced with a digitizer to measure the particle (primary particle) size. Primary particles are independent particles that are not aggregated. The above measurements are carried out for 500 randomly selected particles. The arithmetic mean of the particle sizes of the 500 particles thus obtained is the average particle size of the powder. As the transmission electron microscope, for example, a Hitachi transmission electron microscope H-9000 type can be used. The particle size can be measured using known image analysis software, for example, Carl Zeiss image analysis software KS-400. The average particle size described in the Examples section below is a value measured using a Hitachi transmission electron microscope H-9000 type as the transmission electron microscope and Carl Zeiss image analysis software KS-400 as the image analysis software, unless otherwise specified. In the present invention and this specification, powder means a collection of multiple particles. For example, ferromagnetic powder means a collection of multiple ferromagnetic particles. In addition, the collection of multiple particles is not limited to a form in which the particles constituting the collection are in direct contact with each other, and also includes a form in which a binder, additive, etc., described later, are interposed between the particles. The term particle is sometimes used to refer to powder.
[0055] As a method for collecting sample powder from the magnetic tape for particle size measurement, for example, the method described in paragraph 0015 of JP 2011-048878 A can be used.
[0056] In the present invention and this specification, with respect to the shape of a particle, "plate-like" refers to a shape having two opposing plate surfaces. "Plate surface" refers to a plane observed on the surface of a particle in the above particle photograph and a plane opposite to that plane. On the other hand, among particle shapes that do not have such plate surfaces, a shape with a distinction between a long axis and a short axis is "elliptical". The long axis is determined as the axis (straight line) that can take the longest length of the particle. On the other hand, the short axis is determined as the axis that is the longest when the particle length is taken along a straight line perpendicular to the long axis. A shape in which there is no distinction between the long axis and the short axis, that is, a shape where the long axis length = the short axis length, is "spherical". A shape in which the long axis and the short axis cannot be specified from the shape is called amorphous. In the present invention and this specification, unless otherwise specified, the size of the particles constituting the powder (particle size) is the plate diameter if the shape of the particle observed in the above particle photograph is plate-like, the major axis length if the shape is elliptical, the diameter if the shape is spherical, and the equivalent circle diameter if the shape is irregular. The equivalent circle diameter is determined by the circle projection method.
[0057] For plate-like particles, the "plate thickness" is the longest distance between two opposing plate faces, and the average plate thickness is the arithmetic mean of the values obtained for the 500 particles.
[0058] The content (filling rate) of the ferromagnetic powder in the magnetic layer is preferably in the range of 50 to 90 mass % and more preferably in the range of 60 to 90 mass % relative to the total mass of the magnetic layer. A high filling rate of the ferromagnetic powder in the magnetic layer is preferable from the viewpoint of improving recording density.
[0059] (Binding Agent) The magnetic tape may be a coated magnetic tape, and may contain a binder in the magnetic layer. The binder is one or more kinds of resin. As the binder, various resins that are usually used as binders for coated magnetic tapes may be used. For example, as the binder, a resin selected from polyurethane resin, polyester resin, polyamide resin, vinyl chloride resin, acrylic resin copolymerized with styrene, acrylonitrile, methyl methacrylate, etc., cellulose resin such as nitrocellulose, epoxy resin, phenoxy resin, polyvinyl acetal, polyvinyl butyral, etc. may be used alone or in combination of a plurality of resins. Among these, polyurethane resin, acrylic resin, cellulose resin, and vinyl chloride resin are preferred. These resins may be homopolymers or copolymers. These resins may also be used as binders in the non-magnetic layer and / or backcoat layer described below. For the above binders, reference can be made to paragraphs 0028 to 0031 of JP 2010-24113 A. The average molecular weight of the resin used as the binder can be, for example, 10,000 to 200,000 in weight average molecular weight. The binder can be used in an amount of, for example, 1.0 to 30.0 parts by mass relative to 100.0 parts by mass of the ferromagnetic powder.
[0060] (hardening agent) A curing agent can be used together with the resin usable as a binder. In one embodiment, the curing agent can be a thermosetting compound, which is a compound in which a curing reaction (crosslinking reaction) proceeds by heating, and in another embodiment, the curing agent can be a photocuring compound in which a curing reaction (crosslinking reaction) proceeds by light irradiation. As the curing reaction proceeds in the magnetic layer forming process, at least a part of the curing agent can be contained in the magnetic layer in a state of reacting (crosslinking) with other components such as the binder. This point is also true for layers formed using a composition used to form other layers that contains a curing agent. A preferred curing agent is a thermosetting compound, and polyisocyanate is suitable. For details on polyisocyanate, refer to paragraphs 0124 to 0125 of JP 2011-216149 A. The curing agent can be used in an amount of, for example, 0 to 80.0 parts by mass relative to 100.0 parts by mass of the binder, and preferably 50.0 to 80.0 parts by mass from the viewpoint of improving the strength of the magnetic layer.
[0061] (Additives) The magnetic layer may contain one or more additives as necessary. The additives may be selected from commercially available products according to the desired properties. Alternatively, compounds synthesized by known methods may be used as additives. The additives may be used in any amount. An example of the additive is the above-mentioned curing agent. Examples of additives contained in the magnetic layer include non-magnetic powders (e.g., inorganic powders, carbon black, etc.), lubricants, dispersants, dispersion aids, antifungal agents, antistatic agents, antioxidants, etc. For example, reference may be made to paragraphs 0030 to 0033, 0035, and 0036 of JP-A-2016-126817 for lubricants. The non-magnetic layer described below may contain a lubricant. Reference may be made to paragraphs 0030 to 0031, 0034, 0035, and 0036 of JP-A-2016-126817 for lubricants that may be contained in the non-magnetic layer. For the dispersant, refer to paragraphs 0061 and 0071 of JP-A-2012-133837. The dispersant may be added to the non-magnetic layer forming composition. For the dispersant that can be added to the non-magnetic layer forming composition, refer to paragraph 0061 of JP-A-2012-133837. In addition, examples of non-magnetic powders that can be included in the magnetic layer include non-magnetic powders that can function as abrasives, and non-magnetic powders (e.g., non-magnetic colloidal particles) that can function as protrusion-forming agents that form protrusions that protrude appropriately on the magnetic layer surface. For example, for the abrasives, refer to paragraphs 0030 to 0032 of JP-A-2004-273070. As the protrusion-forming agent, colloidal particles are preferred, and inorganic colloidal particles are preferred from the viewpoint of availability, inorganic oxide colloidal particles are more preferred, and silica colloidal particles (colloidal silica) are even more preferred. The average particle size of each of the abrasive and protrusion-forming agent is preferably in the range of 30 to 200 nm, and more preferably in the range of 50 to 100 nm.
[0062] The magnetic layer described above can be provided directly on the surface of the non-magnetic support, or indirectly via a non-magnetic layer.
[0063] <Nonmagnetic layer> Next, the non-magnetic layer will be described. The magnetic tape may have a magnetic layer directly on the non-magnetic support, or may have a non-magnetic layer containing a non-magnetic powder between the non-magnetic support and the magnetic layer. The non-magnetic powder used in the non-magnetic layer may be a powder of an inorganic substance (inorganic powder) or a powder of an organic substance (organic powder). Carbon black and the like can also be used. Examples of inorganic substances include metals, metal oxides, metal carbonates, metal sulfates, metal nitrides, metal carbides, and metal sulfides. These non-magnetic powders are commercially available, and can also be produced by known methods. For details, refer to paragraphs 0146 to 0150 of JP-A-2011-216149. For carbon black usable in the non-magnetic layer, refer to paragraphs 0040 to 0041 of JP-A-2010-24113. The content (filling rate) of the nonmagnetic powder in the nonmagnetic layer is preferably in the range of 50 to 90 mass %, and more preferably in the range of 60 to 90 mass %, relative to the total mass of the nonmagnetic layer.
[0064] In one embodiment, the non-magnetic layer may contain Fe-based inorganic oxide powder as the non-magnetic powder. In the present invention and this specification, the term "Fe-based inorganic oxide powder" refers to an inorganic oxide powder containing iron as a constituent element. Specific examples of the Fe-based inorganic oxide powder include α-iron oxide powder and goethite powder. In the present invention and this specification, the term "α-iron oxide powder" refers to a non-magnetic powder in which the crystal structure of α-iron oxide is detected as the main phase by X-ray diffraction analysis. α-iron oxide powder is also generally called hematite.
[0065] From the viewpoint of controlling the width direction σ of Sci within the range described above, the nonmagnetic powder for the nonmagnetic layer is selected to have an average particle volume of 2.0×10 -6 μm 3 As a result of the investigations conducted by the present inventors, it has become clear that it is preferable to use the following Fe-based inorganic oxide powder. Therefore, the average particle volume of the Fe-based inorganic oxide powder contained in the nonmagnetic layer is 2.0×10 -6 μm 3 It is preferable that the value is less than 1.5×10 -6 μm3 More preferably, it is 1.0×10 -6 μm 3 The average particle volume is preferably, for example, 1.0×10 -9 μm 3 or more than 1.0×10 -8 μm 3 It can be greater than or less than the values exemplified herein.
[0066] In the present invention and this specification, the above average particle volume is a value determined by the following method. In order to observe the Fe-based inorganic oxide powder contained in the non-magnetic layer of the magnetic tape, the sample is first sliced by a microtome method as a sample pretreatment. The slices are sliced along the longitudinal direction of the magnetic tape so that a slice sample that allows observation of the cross section in the thickness direction of the magnetic tape is obtained. For each of the examples and comparative examples described later, a slice sample was obtained from one of the prepared magnetic tapes using a Leica EM UC6 microtome manufactured by Leica. The obtained thin sample is observed by a transmission electron microscope (TEM) at an acceleration voltage of 300 kV and a total magnification of 200,000 times, so as to include the range from the non-magnetic support to the magnetic layer, and a cross-sectional TEM image is obtained. As the transmission electron microscope, for example, JEOL's JEM-2100Plus can be used. In the examples and comparative examples described later, JEOL's JEM-2100Plus was used as the transmission electron microscope. In the obtained cross-sectional TEM image, 50 particles of the Fe-based inorganic oxide powder are identified from the particles contained in the nonmagnetic layer by using a micro-electron beam diffraction method. Electron beam diffraction by the micro-electron beam diffraction method is performed using a transmission electron microscope at an acceleration voltage of 200 kV and a camera length of 50 cm. In the examples and comparative examples described later, a JEM-2100Plus manufactured by JEOL was used as a transmission electron microscope for electron beam diffraction by the micro-electron beam diffraction method. Thereafter, the average particle volume is calculated as follows using 50 particles of the Fe-based inorganic oxide powder identified as above. First, the major axis length (hereinafter also referred to as "DL") and minor axis length (hereinafter also referred to as "DS") of each particle are measured. The major axis length DL means the maximum distance between two parallel lines drawn at any angle so as to be tangent to the contour of the particle (the so-called maximum Feret's diameter). If the direction of the major axis length defined as above is referred to as the major axis direction, the minor axis length DS means the maximum length of the particle in the direction perpendicular to the major axis direction of the particle. Next, the average major axis length DLave is calculated as the arithmetic mean of the major axis lengths DL of the measured 50 particles. ave is an abbreviation for average. In addition, the average minor axis length DSave is calculated as the arithmetic mean of the minor axis lengths DS of the above 50 particles. The average particle volume Vave is calculated from the average major axis length DLave and the average minor axis length DSave using the following formula. Vave = π / 6 × DSave 2 ×DLave
[0067] In one embodiment, the non-magnetic layer may also contain carbon black as a non-magnetic powder. The average particle size of the carbon black may be, for example, 10 nm or more and 50 nm or less. From the viewpoint of controlling the width direction σ of Sci within the range described above, it has become clear from the results of the study by the present inventor that it is preferable to use carbon black having a pH of 9.0 or less as the non-magnetic powder of the non-magnetic layer. Therefore, the pH of the carbon black contained in the non-magnetic layer is preferably 9.0 or less, more preferably 8.5 or less, and even more preferably 8.0 or less. The above pH may be, for example, 1.0 or more, 2.0 or more, 3.0 or more, 4.0 or more, 5.0 or more, 6.0 or more, or may be less than the value exemplified here.
[0068] For the purposes of this invention and the present specification, the pH of carbon black is determined according to standard test method ASTM D1512.
[0069] The non-magnetic layer has an average grain volume of 2.0×10 -6 μm 3 It is preferable to include at least one of the following Fe-based inorganic oxide powder and carbon black having a pH of 9.0 or less, and more preferable to include both. -6 μm 3 The content of the Fe-based inorganic oxide powder described below can be 50.0 parts by mass or more, 60.0 parts by mass or more, or 70.0 parts by mass or more, and can be, for example, 90.0 parts by mass or less. The content of the carbon black having a pH of 9.0 or less, relative to 100.0 parts by mass of the total amount of nonmagnetic powder contained in the nonmagnetic layer, can be 10.0 parts by mass or more, or 20.0 parts by mass or more, and can be, for example, 50.0 parts by mass or less, 40.0 parts by mass or less, or 30.0 parts by mass or less.
[0070] The non-magnetic layer may contain a binder and may also contain an additive. For other details of the binder, additive, etc. of the non-magnetic layer, known techniques related to non-magnetic layers can be applied. In addition, for example, for the type and content of the binder, the type and content of the additive, known techniques related to magnetic layers can also be applied.
[0071] The non-magnetic layer of the magnetic tape includes a substantially non-magnetic layer that contains a small amount of ferromagnetic powder, for example as an impurity or intentionally, along with the non-magnetic powder. A substantially non-magnetic layer here refers to a layer having a residual magnetic flux density of 10 mT or less, a coercive force of 7.96 kA / m (100 Oe) or less, or a layer having a residual magnetic flux density of 10 mT or less and a coercive force of 7.96 kA / m (100 Oe) or less. It is preferable that the non-magnetic layer has no residual magnetic flux density or coercive force.
[0072] <Nonmagnetic support> Next, the non-magnetic support will be described. Examples of the non-magnetic support (hereinafter, simply referred to as "support") include known biaxially stretched polyethylene terephthalate, polyethylene naphthalate, polyamide, polyamideimide, aromatic polyamide, and the like. Among these, polyethylene terephthalate, polyethylene naphthalate, and polyamide are preferred. These supports may be previously subjected to corona discharge, plasma treatment, easy-adhesion treatment, heat treatment, and the like.
[0073] In one embodiment, the non-magnetic support of the magnetic tape may be an aromatic polyester support. In the present invention and this specification, "aromatic polyester" means a resin containing an aromatic skeleton and a plurality of ester bonds, and "aromatic polyester support" means a support containing at least one layer of aromatic polyester film. "Aromatic polyester film" means a film in which the component that constitutes this film in the largest proportion by mass is an aromatic polyester. In the present invention and this specification, the "aromatic polyester support" includes a support in which all the resin films contained in this support are aromatic polyester films, and a support containing an aromatic polyester film and another resin film. Specific forms of the aromatic polyester support include a single-layer aromatic polyester film, a laminated film of two or more layers of aromatic polyester films having the same constituent components, a laminated film of two or more layers of aromatic polyester films having different constituent components, a laminated film containing one or more layers of aromatic polyester films and one or more layers of resin films other than aromatic polyesters, and the like. In the laminated film, an adhesive layer or the like may be optionally included between two adjacent layers. In addition, the aromatic polyester support may optionally include a metal film and / or a metal oxide film formed by deposition or the like on one or both surfaces. The above also applies to the "polyethylene terephthalate support" and the "polyethylene naphthalate support" in the present invention and this specification.
[0074] The aromatic ring contained in the aromatic skeleton of the aromatic polyester is not particularly limited, but specific examples of the aromatic ring include a benzene ring and a naphthalene ring. For example, polyethylene terephthalate (PET) is a polyester containing a benzene ring, and is a resin obtained by polycondensation of ethylene glycol with terephthalic acid and / or dimethyl terephthalate. In the present invention and this specification, "polyethylene terephthalate" also includes structures having one or more other components (e.g., copolymerized components, components introduced into the terminals or side chains, etc.) in addition to the above components. Polyethylene naphthalate (PEN) is a polyester containing a naphthalene ring, and is a resin obtained by esterification of dimethyl 2,6-naphthalenedicarboxylate with ethylene glycol, followed by transesterification and polycondensation. In the present invention and this specification, "polyethylene naphthalate" also includes structures having one or more other components (e.g., copolymer components, components introduced into the terminals or side chains, etc.) in addition to the above components.
[0075] In one embodiment, the non-magnetic support of the magnetic tape can be an aromatic polyamide support. In the present invention and this specification, "aromatic polyamide" means a resin containing an aromatic skeleton and a plurality of amide bonds. The aromatic ring contained in the aromatic skeleton of the aromatic polyamide is not particularly limited. Specific examples of aromatic rings include, for example, a benzene ring. "Aromatic polyamide support" means a support containing at least one layer of aromatic polyamide film. "Aromatic polyamide film" means a film in which the component that is the most abundant component by mass among the components constituting this film is aromatic polyamide. The "aromatic polyamide support" in the present invention and this specification includes a support in which all the resin films contained in this support are aromatic polyamide films, and a support containing an aromatic polyamide film and another resin film. Specific forms of the aromatic polyamide support include a single layer aromatic polyamide film, a laminated film of two or more layers of aromatic polyamide films having the same constituent components, a laminated film of two or more layers of aromatic polyamide films having different constituent components, a laminated film containing one or more layers of aromatic polyamide films and one or more layers of resin films other than aromatic polyamide, and the like. The laminated film may optionally include an adhesive layer between two adjacent layers. The aromatic polyamide support may optionally include a metal film and / or a metal oxide film formed by deposition or the like on one or both surfaces.
[0076] As described above, the non-magnetic support may be a biaxially stretched film, and may be a film that has been subjected to corona discharge, plasma treatment, easy-adhesion treatment, heat treatment, or the like.
[0077] An example of an index of the physical properties of a non-magnetic support is its moisture content. In the present invention and this specification, the moisture content of a non-magnetic support is a value determined by the following method. A sample piece (e.g., a sample piece having a mass of several grams) cut out from the non-magnetic support for which moisture content is to be measured is dried until it reaches a constant weight in a vacuum dryer at a temperature of 180° C. and a pressure of 100 Pa (pascals) or less. The mass of the sample piece thus dried is designated as W1. W1 is a value measured in a measurement environment at a temperature of 23° C. and a relative humidity of 50% within 30 seconds after it is removed from the vacuum dryer. Next, W2 is the mass of the sample piece after it is placed in an environment at a temperature of 25° C. and a relative humidity of 75% for 48 hours. W2 is a value measured in a measurement environment at a temperature of 23° C. and a relative humidity of 50% within 30 seconds after it is removed from the environment. The moisture content is calculated by the following formula. Moisture content (%)=[(W2-W1) / W1]×100 For example, after removing the portions other than the non-magnetic support, such as the magnetic layer, from the magnetic tape by a known method (such as removal of the film using an organic solvent), the water content of the non-magnetic support can be determined by the above method.
[0078] In one embodiment, the moisture content of the non-magnetic support of the magnetic tape is preferably 2.0% or less, more preferably 1.8% or less, even more preferably 1.6% or less, even more preferably 1.4% or less, even more preferably 1.2% or less, and even more preferably 1.0% or less. The moisture content of the non-magnetic support of the magnetic tape can be 0%, 0% or more, more than 0%, or 0.1% or more.
[0079] Young's modulus can also be mentioned as an index of the physical properties of a non-magnetic support. In the present invention and this specification, the Young's modulus of a non-magnetic support is a value measured by the following method in a measurement environment of a temperature of 23° C. and a relative humidity of 50%. A sample piece cut out from the non-magnetic support to be measured is pulled by a universal tensile tester under the conditions of a chuck distance of 100 mm, a pulling speed of 10 mm / min, and a chart speed of 500 mm / min. As the universal tensile tester, for example, a commercially available universal tensile tester such as Toyo Baldwin's Tensilon or a universal tensile tester of a known configuration can be used. From the tangent of the rising part of the load-elongation curve thus obtained, the Young's modulus in the longitudinal direction and the width direction of the sample piece are calculated. Here, the longitudinal direction and the width direction of the sample piece refer to the longitudinal direction and the width direction when the sample piece is included in a magnetic tape. For example, after removing the portions other than the non-magnetic support, such as the magnetic layer, from the magnetic tape by a known method (e.g., removal using an organic solvent), the Young's modulus in the longitudinal and transverse directions of the non-magnetic support can be determined by the above method.
[0080] In one embodiment, the Young's modulus of the non-magnetic support of the magnetic tape in the longitudinal direction is preferably 3000 MPa or more, more preferably 4000 MPa or more, even more preferably 5000 MPa or more, and even more preferably 6000 MPa or more. The Young's modulus of the non-magnetic support of the magnetic tape in the longitudinal direction can be 15000 MPa or less, 13000 MPa or less, or 12000 MPa or less. In the width direction, the Young's modulus of the non-magnetic support of the magnetic tape in the width direction is preferably 2000 MPa or more, more preferably 3000 MPa or more, even more preferably 4000 MPa or more, and even more preferably 5000 MPa or more. The Young's modulus of the non-magnetic support of the magnetic tape in the width direction can be 12000 MPa or less, 11000 MPa or less, or 10000 MPa or less. When manufacturing a magnetic tape, the non-magnetic support is usually used with the MD direction (machine direction) of the film as the longitudinal direction and the TD direction (transverse direction) as the width direction. In one embodiment, the Young's modulus in the longitudinal direction is preferably larger than the Young's modulus in the width direction, and the difference (Young's modulus in the longitudinal direction - Young's modulus in the width direction) is more preferably in the range of 800 to 3000 MPa.
[0081] The water content and Young's modulus of the nonmagnetic support can be controlled by the types and mixing ratios of the components constituting the support, the manufacturing conditions of the support, etc. For example, by adjusting the stretching ratio in each direction in the biaxial stretching process, the Young's modulus in the longitudinal direction and the Young's modulus in the transverse direction can be controlled, respectively.
[0082] <Backcoat layer> The magnetic tape may or may not have a backcoat layer containing a nonmagnetic powder on the surface side of the nonmagnetic support opposite to the surface side having the magnetic layer. For the nonmagnetic powder in the backcoat layer, for example, see the above description of the nonmagnetic powder in the nonmagnetic layer.
[0083] The surface shape of the magnetic layer may be affected by the transfer of the surface shape of the back surface to the magnetic layer surface (so-called show-through) when the magnetic layer surface and the back surface are in contact with each other in a rolled state during the manufacturing process of the magnetic tape. The back surface is the backcoat layer surface when the magnetic layer has a backcoat layer, and is the support surface when the magnetic layer does not have a backcoat layer. As for Sci and the width direction σ of Sci of the magnetic layer surface, the inventor's study revealed that it is preferable for the non-magnetic powder of the backcoat layer to be a non-magnetic powder composed of plate-shaped particles from the viewpoint of controlling Sci and the width direction σ of Sci of the magnetic layer surface within the range described above. Furthermore, the inventor's study revealed that, from the viewpoint of controlling Sci and the width direction σ of Sci of the magnetic layer surface within the range described above, it is more preferable for the non-magnetic powder of the backcoat layer to be a non-magnetic powder having an average plate diameter of 50 nm or more and 1000 nm or less and an average plate thickness of 12 nm or less. The average plate thickness can be, for example, 3 nm or more, 4 nm or more, or 5 nm or more, and can be less than the value exemplified here. The non-magnetic powder composed of plate-like particles (preferably a non-magnetic powder having an average plate diameter of 50 nm to 1000 nm and an average plate thickness of 12 nm or less) can be, for example, a metal oxide powder. Specific examples of metal oxides include aluminum oxide, zirconium oxide, and cerium oxide. Aluminum oxide is also called alumina, zirconium oxide is also called zirconia, and cerium oxide is also called ceria. For example, a metal hydroxide aqueous solution can be heated to a liquid temperature of 200° C. or higher to allow a hydrothermal synthesis reaction to proceed, thereby obtaining plate-like metal oxide particles. The plate diameter and plate thickness of the plate-like particles can be controlled by adjusting various conditions for particle preparation (for example, the concentration of the aqueous solution, the mixing time during preparation of the aqueous solution, the heating temperature, the heating time, etc.).
[0084] The content (filling rate) of the nonmagnetic powder in the backcoat layer is preferably in the range of 50 to 90 mass %, and more preferably in the range of 60 to 90 mass %, relative to the total mass of the backcoat layer.
[0085] The composition for forming a backcoat layer preferably contains a component (dispersant) capable of improving the dispersibility of the non-magnetic powder contained in the composition. The present inventors speculate that forming a backcoat layer using a composition for forming a backcoat layer containing such a dispersant is preferable from the viewpoint of reducing the effect of show-through and controlling the Sci and width direction σ of Sci on the magnetic layer surface within the range described above. As an example of such a dispersant, a compound having an ammonium salt structure of an alkyl ester anion represented by the following formula 1 can be used. The "alkyl ester anion" can also be called an "alkyl carboxylate anion".
[0086] [ka]
[0087] In formula 1, R represents an alkyl group having 7 or more carbon atoms or a fluorinated alkyl group having 7 or more carbon atoms; Z + represents an ammonium cation.
[0088] In addition, from the viewpoint of improving the dispersibility of the non-magnetic powder, in one embodiment, two or more components capable of forming a compound having the above-mentioned salt structure can be used when preparing the composition for forming the backcoat layer, whereby at least a part of the components can form a compound having the above-mentioned salt structure when preparing the composition for forming the backcoat layer.
[0089] Unless otherwise specified, the groups described below may have a substituent or may be unsubstituted. In addition, the "carbon number" of a group having a substituent means the carbon number not including the carbon number of the substituent, unless otherwise specified. In the present invention and this specification, examples of the substituent include an alkyl group (e.g., an alkyl group having 1 to 6 carbon atoms), a hydroxyl group, an alkoxy group (e.g., an alkoxy group having 1 to 6 carbon atoms), a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, etc.), a cyano group, an amino group, a nitro group, an acyl group, a carboxy group, a salt of a carboxy group, a sulfonic acid group, a salt of a sulfonic acid group, etc.
[0090] Formula 1 will now be described in more detail.
[0091] In formula 1, R represents an alkyl group having 7 or more carbon atoms or a fluorinated alkyl group having 7 or more carbon atoms. The fluorinated alkyl group has a structure in which some or all of the hydrogen atoms constituting the alkyl group are substituted with fluorine atoms. The alkyl group or fluorinated alkyl group represented by R may have a straight-chain structure, may have a branched structure, or may be a cyclic alkyl group or fluorinated alkyl group, and is preferably a straight-chain structure. The alkyl group or fluorinated alkyl group represented by R may have a substituent or may be unsubstituted, and is preferably unsubstituted. The alkyl group represented by R is, for example, C n H 2n+1 Here, n is an integer of 7 or more. The fluorinated alkyl group represented by R can be, for example, C n H 2n+1 The alkyl group or fluorinated alkyl group represented by R may have a structure in which some or all of the hydrogen atoms constituting the alkyl group represented by - are substituted with fluorine atoms. The number of carbon atoms in the alkyl group or fluorinated alkyl group represented by R is 7 or more, preferably 8 or more, more preferably 9 or more, even more preferably 10 or more, still more preferably 11 or more, even more preferably 12 or more, and even more preferably 13 or more. The number of carbon atoms in the alkyl group or fluorinated alkyl group represented by R is preferably 20 or less, more preferably 19 or less, and even more preferably 18 or less.
[0092] In equation 1, Z + represents an ammonium cation. More specifically, the ammonium cation has the following structure: In the present invention and this specification, an asterisk in a formula representing a part of a compound represents a bonding position between the part of the structure and an adjacent atom.
[0093] [ka]
[0094] Nitrogen cation N of ammonium cation + and the oxygen anion O in Eq. - and form a salt bridging group to form an ammonium salt structure of an alkyl ester anion represented by formula 1. The inclusion of a compound having an ammonium salt structure of an alkyl ester anion represented by formula 1 in the backcoat layer can be confirmed by analyzing the magnetic tape using X-ray photoelectron spectroscopy (ESCA: Electron Spectroscopy for Chemical Analysis), infrared spectroscopy (IR: infrared spectroscopy), etc.
[0095] In one form, Z + The ammonium cation represented by the formula (I) can be obtained, for example, by the nitrogen atom of a nitrogen-containing polymer becoming a cation. The nitrogen-containing polymer means a polymer containing a nitrogen atom. In the present invention and this specification, the terms "polymer" and "polymeric polymer" are used to include homopolymers and copolymers. In one form, the nitrogen atom can be included as an atom constituting the main chain of the polymer, and in another form, the nitrogen atom can be included as an atom constituting the side chain of the polymer.
[0096] One example of the nitrogen-containing polymer is polyalkyleneimine, which is a ring-opening polymer of alkyleneimine and has a plurality of repeating units represented by the following formula 2.
[0097] [ka]
[0098] The nitrogen atom N constituting the main chain in formula 2 is a nitrogen cation N + So, Z in Eq. + This can result in an ammonium cation represented by the formula: and can form an ammonium salt structure with an alkyl ester anion, for example as follows:
[0099] [ka]
[0100] Formula 2 will now be described in more detail.
[0101] In formula 2, R 1 and R 2 each independently represents a hydrogen atom or an alkyl group, and n1 represents an integer of 2 or greater.
[0102] R 1 or R 2 Examples of the alkyl group represented by the formula (I) include alkyl groups having 1 to 6 carbon atoms, preferably alkyl groups having 1 to 3 carbon atoms, more preferably a methyl group or an ethyl group, and even more preferably a methyl group. 1 or R 2 The alkyl group represented by the formula (2) is preferably an unsubstituted alkyl group. 1 and R 2The combination of includes a form in which one is a hydrogen atom and the other is an alkyl group, a form in which both are hydrogen atoms, and a form in which both are alkyl groups (same or different alkyl groups), and preferably a form in which both are hydrogen atoms. As an alkyleneimine that results in a polyalkyleneimine, the structure with the smallest number of carbon atoms constituting the ring is ethyleneimine, and the number of carbon atoms in the main chain of the alkyleneimine (ethyleneimine) obtained by ring-opening of ethyleneimine is 2. Therefore, n1 in formula 2 is 2 or more. n1 in formula 2 can be, for example, 10 or less, 8 or less, 6 or less, or 4 or less. The polyalkyleneimine may be a homopolymer containing only the same structure as the repeating structure represented by formula 2, or a copolymer containing two or more different structures as the repeating structure represented by formula 2. The number average molecular weight of the polyalkyleneimine that can be used to form a compound having an ammonium salt structure of an alkyl ester anion represented by formula 1 can be, for example, 200 or more, preferably 300 or more, and more preferably 400 or more. The number average molecular weight of the polyalkyleneimine can be, for example, 10,000 or less, preferably 5,000 or less, and more preferably 2,000 or less.
[0103] In the present invention and this specification, the average molecular weight (weight average molecular weight and number average molecular weight) refers to a value measured by gel permeation chromatography (GPC) and calculated in terms of standard polystyrene. The average molecular weight shown in the Examples section below is a value (polystyrene-equivalent value) calculated in terms of standard polystyrene from a value measured using GPC under the following measurement conditions, unless otherwise specified. GPC equipment: HLC-8220 (Tosoh Corporation) Guard column: TSKguardcolumn Super HZM-H Columns: TSKgel Super HZ 2000, TSKgel Super HZ 4000, TSKgel Super HZ-M (Tosoh Corporation, 4.6 mm (inner diameter) x 15.0 cm, three columns connected in series) Eluent: Tetrahydrofuran (THF), containing stabilizer (2,6-di-t-butyl-4-methylphenol) Eluent flow rate: 0.35mL / min Column temperature: 40℃ Inlet temperature: 40℃ Refractive Index (RI) measurement temperature: 40℃ Sample concentration: 0.3% by mass Sample injection volume: 10 μL
[0104] Another example of the nitrogen-containing polymer is polyallylamine, which is a polymer of allylamine and has a plurality of repeating units represented by the following formula 3.
[0105] [ka]
[0106] The nitrogen atom N constituting the amino group in the side chain in formula 3 is a nitrogen cation N + So, Z in Eq. + This can result in an ammonium cation represented by the formula: and can form an ammonium salt structure with an alkyl ester anion, for example as follows:
[0107] [ka]
[0108] The weight-average molecular weight of the polyallylamine usable for forming the compound having the ammonium salt structure of the alkyl ester anion represented by formula 1 can be, for example, 200 or more, preferably 1,000 or more, and more preferably 1,500 or more. The weight-average molecular weight of the polyallylamine can be, for example, 15,000 or less, preferably 10,000 or less, and more preferably 8,000 or less.
[0109] The presence of a compound having a structure derived from polyalkyleneimine or polyallylamine in the backcoat layer as a compound having an ammonium salt structure of an alkyl ester anion represented by formula 1 can be confirmed by analyzing the surface of the backcoat layer using time-of-flight secondary ion mass spectrometry (TOF-SIMS) or the like.
[0110] The compound having an ammonium salt structure of an alkyl ester anion represented by formula 1 can be a salt of a nitrogen-containing polymer and one or more fatty acids selected from the group consisting of fatty acids having 7 or more carbon atoms and fluorinated fatty acids having 7 or more carbon atoms. The nitrogen-containing polymer forming the salt can be one or more nitrogen-containing polymers, for example, a nitrogen-containing polymer selected from the group consisting of polyalkyleneimine and polyallylamine. The fatty acids forming the salt can be one or more fatty acids selected from the group consisting of fatty acids having 7 or more carbon atoms and fluorinated fatty acids having 7 or more carbon atoms. The fluorinated fatty acid has a structure in which some or all of the hydrogen atoms constituting the alkyl group bonded to the carboxy group COOH in the fatty acid are replaced with fluorine atoms. For example, the salt-forming reaction can easily proceed by mixing the nitrogen-containing polymer and the above-mentioned fatty acids at room temperature. The room temperature is, for example, about 20 to 25°C. In one embodiment, one or more nitrogen-containing polymers and one or more fatty acids are used as components of the composition for forming a backcoat layer, and the salt-forming reaction can be promoted by mixing them in the preparation process of the composition for forming a backcoat layer. In another embodiment, before preparing the composition for forming a backcoat layer, one or more nitrogen-containing polymers and one or more fatty acids are mixed to form a salt, and then the salt can be used as a component of the composition for forming a backcoat layer to prepare the composition for forming a backcoat layer. When mixing the nitrogen-containing polymer and the fatty acids to form the ammonium salt of the alkyl ester anion represented by formula 1, the nitrogen atom constituting the nitrogen-containing polymer and the carboxyl group of the fatty acid may also react to form the following structure, and the form including such a structure is also included in the above compound.
[0111] [ka]
[0112] Examples of the fatty acids include fatty acids having an alkyl group as described above for R in formula 1 and fluorinated fatty acids having a fluorinated alkyl group as described above for R in formula 1.
[0113] The mixing ratio of the nitrogen-containing polymer and the fatty acid used to form the compound having an ammonium salt structure of an alkyl ester anion represented by formula 1 is preferably 10:90 to 90:10, more preferably 20:80 to 85:15, and even more preferably 30:70 to 80:20, as the mass ratio of the nitrogen-containing polymer: the fatty acid. In addition, the compound having an ammonium salt structure of an alkyl ester anion represented by formula 1 can be used, for example, 1.0 to 20.0 parts by mass, and preferably 1.0 to 10.0 parts by mass, per 100.0 parts by mass of the nonmagnetic powder when preparing the composition for forming the backcoat layer. In addition, for example, in the preparation of the composition for forming the backcoat layer, 0.1 to 10.0 parts by mass of the nitrogen-containing polymer can be used, and preferably 0.2 to 8.0 parts by mass of the nitrogen-containing polymer can be used, per 100.0 parts by mass of the nonmagnetic powder. The fatty acids can be used in an amount of, for example, 0.05 to 10.0 parts by mass, and preferably 0.1 to 5.5 parts by mass, per 100.0 parts by mass of the nonmagnetic powder.
[0114] Regarding the components that can be contained in the backcoat layer, the backcoat layer can include a binder and can also include additives. For the binder and additives of the backcoat layer, known techniques related to the backcoat layer can be applied, and known techniques related to the formulation of the magnetic layer and / or nonmagnetic layer can also be applied. For example, the descriptions of the backcoat layer can be referred to in paragraphs 0018-0020 of JP 2006-331625 A and in column 4, line 65 to column 5, line 38 of U.S. Patent No. 7,029,774.
[0115] <Various thicknesses> Regarding the thickness (total thickness) of the magnetic tape, with the enormous increase in the amount of information in recent years, there is a demand for magnetic recording media to have higher recording capacity (higher capacity). As a means for increasing the capacity of tape-shaped magnetic recording media (i.e., magnetic tape), there is the reduction in the thickness of the magnetic tape and the increase in the length of the magnetic tape accommodated in one magnetic tape cartridge. From this point of view, the thickness (total thickness) of the magnetic tape is preferably 5.6 μm or less, more preferably 5.5 μm or less, even more preferably 5.4 μm or less, even more preferably 5.3 μm or less, even more preferably 5.2 μm or less, even more preferably 5.0 μm or less, and even more preferably 4.8 μm or less. From the viewpoint of ease of handling, the thickness of the magnetic tape is preferably 3.0 μm or more, more preferably 3.5 μm or more, and even more preferably 4.0 μm or more.
[0116] The thickness (total thickness) of the magnetic tape can be measured by the following method. Ten samples (e.g., 5 to 10 cm long) are cut out from any part of the magnetic tape, and the samples are stacked and the thickness is measured. The measured thickness is divided by 10 to obtain the value (thickness per sample), which is the total thickness. The thickness measurement can be performed using a known measuring device capable of measuring thickness to the order of 0.1 μm.
[0117] The thickness of the nonmagnetic support is preferably 2.0 to 5.0 μm, and more preferably 3.0 to 5.0 μm. The thickness of the magnetic layer can be optimized according to the saturation magnetization amount of the magnetic head used, the head gap length, the band of the recording signal, etc., and is generally 0.01 μm to 0.15 μm, and from the viewpoint of high-density recording, is preferably 0.02 μm to 0.12 μm, and more preferably 0.03 μm to 0.1 μm. At least one magnetic layer is sufficient, and the magnetic layer may be separated into two or more layers having different magnetic properties, and a known configuration related to a multilayer magnetic layer can be applied. When the magnetic layer is separated into two or more layers, the thickness of the magnetic layer is the total thickness of these layers. The thickness of the nonmagnetic layer is, for example, 0.1 to 1.5 μm, preferably 0.1 to 1.0 μm, and more preferably 0.1 to 0.7 μm. The thickness of the backcoat layer is preferably 0.9 μm or less, and more preferably 0.1 to 0.7 μm. Various thicknesses such as the thickness of the magnetic layer can be determined by the following method. After exposing the cross section of the magnetic tape in the thickness direction with an ion beam, the exposed cross section is observed with a scanning electron microscope or a transmission electron microscope. The thicknesses can be calculated as the arithmetic average of the thicknesses measured at any two points in the cross section observation. Alternatively, the thicknesses can be calculated as the design thickness calculated from the manufacturing conditions, etc.
[0118] <Manufacturing process> (Preparation of compositions for forming each layer) The composition for forming the magnetic layer, non-magnetic layer or backcoat layer usually contains a solvent in addition to the various components described above. As the solvent, one or more of the various solvents usually used in the manufacture of coating-type magnetic recording media can be used. The solvent content of each layer-forming composition is not particularly limited. For the solvent, refer to paragraph 0153 of JP 2011-216149 A. The solid content concentration and solvent composition of each layer-forming composition may be appropriately adjusted according to the handling suitability of the composition, the coating conditions and the thickness of each layer to be formed. The process for preparing the composition for forming the magnetic layer, non-magnetic layer or backcoat layer usually includes at least a kneading process, a dispersing process, and a mixing process provided before or after these processes as necessary. Each individual process may be divided into two or more stages. The various components used in the preparation of each layer-forming composition may be added at the beginning or during any process. Also, each individual component may be added in two or more steps in a divided manner. For example, the binder may be added in a divided manner in the kneading process, the dispersing process and the mixing process for adjusting the viscosity after dispersion. In the manufacturing process of the magnetic tape, conventional known manufacturing techniques can be used as part of the process. In the kneading process, a device having a strong kneading force such as an open kneader, a continuous kneader, a pressure kneader, or an extruder can be used. Details of the kneading process are described in JP-A-1-106338 and JP-A-1-79274. As the dispersing machine, various known dispersing machines utilizing shear force such as a bead mill, a ball mill, a sand mill, or a homomixer can be used. Dispersing beads can be preferably used for dispersion. Examples of dispersing beads include ceramic beads and glass beads, and zirconia beads are preferred. Two or more types of beads may be used in combination. The bead diameter (particle size) and bead packing rate of the dispersing beads are not particularly limited, and may be set according to the powder to be dispersed. The dispersion time is not particularly limited. From the viewpoint of reducing the effect of back-transmission and controlling the Sci and width direction σ of Sci on the magnetic layer surface within the range described above, the present inventors speculate that it is preferable to improve the dispersibility of the non-magnetic powder in the composition for forming the backcoat layer.From the viewpoint of improving the dispersibility of the non-magnetic powder in the composition for forming a backcoat layer, it is preferable to extend the dispersion time in the preparation of the composition for forming a backcoat layer. Each layer-forming composition may be filtered by a known method before being subjected to the coating process. The filtration can be performed, for example, by filter filtration. As the filter used for filtration, for example, a filter with a pore size of 0.01 to 3 μm (for example, a glass fiber filter, a polypropylene filter, etc.) can be used.
[0119] (Coating process, cooling process, heating and drying process) The magnetic layer can be formed by directly applying the magnetic layer-forming composition onto the non-magnetic support, or by sequentially or simultaneously applying the magnetic layer-forming composition and the non-magnetic layer-forming composition in a multilayer manner. For details on the coating for forming each layer, see paragraph 0066 of JP2010-231843A.
[0120] As described above, in one embodiment, the magnetic tape can have a non-magnetic layer between the non-magnetic support and the magnetic layer. Such a magnetic tape can preferably be manufactured by successive multi-layer coating. The manufacturing process of performing successive multi-layer coating can preferably be carried out as follows. The non-magnetic layer is formed through a coating process in which a non-magnetic layer-forming composition is applied to a non-magnetic support to form a coating layer, and a heat-drying process in which the formed coating layer is dried by heat treatment. Then, a magnetic layer is formed through a coating process in which a magnetic layer-forming composition is applied to the formed non-magnetic layer to form a coating layer, and a heat-drying process in which the formed coating layer is dried by heat treatment. In one embodiment, in the non-magnetic layer forming process of the manufacturing method performing successive multi-layer coating, a coating process is performed using a non-magnetic layer-forming composition to form a coating layer, and a cooling process of cooling the coating layer can also be performed between the coating process and the heat-drying process.
[0121] An example of a manufacturing process for the magnetic tape will be described below with reference to Fig. 8. However, the present invention is not limited to the following example.
[0122] Fig. 8 is a process schematic diagram showing an example of a process for producing a magnetic tape having a nonmagnetic layer and a magnetic layer in this order on one side of a nonmagnetic support and a backcoat layer on the other side. In the example shown in Fig. 8, the nonmagnetic support (long film) is continuously wound from the unwinding section to the winding section, and various treatments such as coating, drying, and orientation are performed in each section or zone shown in Fig. 8, so that a nonmagnetic layer and a magnetic layer can be formed by successive multilayer coating on one side of the running nonmagnetic support, and a backcoat layer can be formed on the other side. The example shown in Fig. 8 can be the same as a manufacturing process usually performed for the production of coating-type magnetic recording media, except that a cooling zone is included.
[0123] In the first coating section, the nonmagnetic support delivered from the delivery section is coated with a nonmagnetic layer forming composition (a step of applying the nonmagnetic layer forming composition).
[0124] After the coating step, the coating layer of the nonmagnetic layer-forming composition formed in the coating step is cooled in a cooling zone (cooling step). For example, the cooling step can be performed by passing the nonmagnetic support on which the coating layer is formed through a cooling atmosphere. The temperature of the cooling atmosphere can be preferably in the range of -10°C to 0°C, and more preferably in the range of -5°C to 0°C. The time for performing the cooling step (for example, the time from when any part of the coating layer is carried into the cooling zone until it is carried out (hereinafter, also referred to as "residence time")) is not particularly limited. In the cooling step, cooled gas may be blown onto the surface of the coating layer.
[0125] After the cooling zone, in the first heat treatment zone, the coating layer after the cooling step is heated to dry the coating layer (heat drying step). The heat drying step can be performed by passing the non-magnetic support having the coating layer after the cooling step through a heated atmosphere. The temperature of the heated atmosphere here, as well as the temperature of the heated atmosphere in the heat drying step in the second heat treatment zone and the heat drying step in the third heat treatment zone described below, are also called "drying temperature". In one embodiment, the drying temperature in each heat treatment zone is preferably 95°C or higher, more preferably 100°C or higher. The drying temperature in each heat treatment zone can be, for example, 140°C or lower or 130°C or lower, and can also be higher than the temperatures listed here. Optionally, heated gas may be blown onto the surface of the coating layer.
[0126] Next, in the second coating section, a magnetic layer-forming composition is coated onto the non-magnetic layer formed by the heat drying step in the first heat treatment zone (magnetic layer-forming composition coating step).
[0127] In the case of carrying out the orientation treatment after that, while the coating layer of the magnetic layer forming composition is in a wet state, the ferromagnetic powder in the coating layer is oriented in the orientation zone. For the orientation treatment, various known techniques, including those described in paragraph 0067 of JP 2010-231843 A, can be applied. For example, the vertical orientation treatment can be carried out by a known method, such as a method using magnets with opposite poles facing each other. In the orientation zone, the drying speed of the coating layer can be controlled by the temperature and volume of the drying air and / or the transport speed of the magnetic tape in the orientation zone. In addition, the coating layer may be pre-dried before being transported to the orientation zone.
[0128] The coated layer after the orientation treatment is subjected to a heat drying step in the second heat treatment zone.
[0129] Next, in the third coating section, a backcoat layer forming composition is applied to the surface of the non-magnetic support opposite to the surface on which the non-magnetic layer and the magnetic layer are formed, forming a coating layer (a backcoat layer forming composition application step).Then, in the third heat treatment zone, the coating layer is heat treated and dried.
[0130] Through the above steps, a magnetic tape can be obtained which has a nonmagnetic layer and a magnetic layer in that order on one side of a nonmagnetic support and a backcoat layer on the other side.
[0131] (Other processes) In the manufacturing process of magnetic tapes, calendering is usually performed to improve the surface smoothness of the magnetic tape. Strengthening the calendering conditions can contribute to reducing the value of the width direction σ of Sci. Specific examples of strengthening the calendering conditions include increasing the calendering pressure, increasing the calendering temperature, and decreasing the calendering speed. Regarding the calendering conditions, the calendering pressure (linear pressure) is preferably 300 to 500 kN / m, more preferably 310 to 350 kN / m, the calendering temperature (surface temperature of the calender roll) is preferably 95 to 120° C., more preferably 100 to 120° C., and the calendering speed is preferably 50 to 75 m / min. For other various steps in manufacturing the magnetic tape, reference can be made to paragraphs 0067 to 0070 of JP2010-231843A. A long magnetic tape roll can be obtained through various processes. The obtained magnetic tape roll is cut (slit) to the width of the magnetic tape to be housed in a magnetic tape cartridge, for example, by a known cutter. The width can be determined according to standards and is usually 1 / 2 inch. 1 inch = 2.54 cm. A servo pattern is usually formed on the magnetic tape obtained by slitting.
[0132] (Formation of servo pattern) “Formation of a servo pattern” can also be called “recording of a servo signal.” The formation of a servo pattern will be described below.
[0133] The servo pattern is usually formed along the longitudinal direction of the magnetic tape. Control methods that use servo signals (servo control) include timing-based servo (TBS), amplitude servo, and frequency servo.
[0134] As shown in ECMA (European Computer Manufacturers Association)-319 (June 2001), magnetic tapes (generally called "LTO tapes") conforming to the LTO (Linear Tape-Open) standard employ a timing-based servo system. In this timing-based servo system, a servo pattern is formed by a pair of non-parallel magnetic stripes (also called "servo stripes") arranged continuously in the longitudinal direction of the magnetic tape. In this invention and this specification, the "timing-based servo pattern" refers to a servo pattern that enables head tracking in a servo system of the timing-based servo system. As described above, the servo pattern is formed by a pair of non-parallel magnetic stripes in order to inform the servo signal reading element passing over the servo pattern of its passing position. Specifically, the pair of magnetic stripes is formed so that the interval between them changes continuously along the width direction of the magnetic tape, and the servo signal reading element can know the relative position between the servo pattern and the servo signal reading element by reading the interval. This relative position information enables tracking of the data track. For this reason, a plurality of servo tracks are usually set on the servo pattern along the width direction of the magnetic tape.
[0135] A servo band is made up of a continuous servo pattern in the longitudinal direction of the magnetic tape. Usually, multiple servo bands are provided on a magnetic tape. For example, there are five servo bands on an LTO tape. The area between two adjacent servo bands is the data band. The data band is made up of multiple data tracks, and each data track corresponds to one servo track.
[0136] Also, in one embodiment, as shown in JP 2004-318983 A, information indicating the number of the servo band (also called "servo band ID (identification)" or "UDIM (Unique Data Band Identification Method) information") is embedded in each servo band. This servo band ID is recorded by shifting a specific one of a plurality of pairs of servo stripes in the servo band so that its position is displaced relatively in the longitudinal direction of the magnetic tape. Specifically, the way in which a specific one of a plurality of pairs of servo stripes is shifted is changed for each servo band. As a result, the recorded servo band ID is unique for each servo band, so that the servo band can be uniquely identified simply by reading one servo band with a servo signal reading element.
[0137] As a method for uniquely identifying servo bands, there is also a method using the staggered method as shown in ECMA-319 (June 2001). In this staggered method, a group of pairs of non-parallel magnetic stripes (servo stripes) arranged continuously in the longitudinal direction of the magnetic tape are recorded so that they are shifted in the longitudinal direction of the magnetic tape for each servo band. The combination of the shift between adjacent servo bands is unique across the entire magnetic tape, so when the servo pattern is read by two servo signal reading elements, it is possible to uniquely identify the servo bands.
[0138] Also, as specified in ECMA-319 (June 2001), information indicating the longitudinal position of the magnetic tape (also called "LPOS (Longitudinal Position) information") is usually embedded in each servo band. Like UDIM information, this LPOS information is also recorded by shifting the positions of a pair of servo stripes in the longitudinal direction of the magnetic tape. However, unlike UDIM information, the same signal is recorded in each servo band with this LPOS information.
[0139] It is also possible to embed information other than the above UDIM information and LPOS information in the servo bands. In this case, the embedded information may be different for each servo band, such as UDIM information, or may be common to all servo bands, such as LPOS information. Also, methods other than those described above can be used to embed information in the servo bands. For example, a predetermined code may be recorded by thinning out a predetermined pair from a group of pairs of servo stripes.
[0140] The head for forming a servo pattern is called a servo write head. The servo write head usually has a pair of gaps corresponding to the pair of magnetic stripes, the number of which is equal to the number of servo bands. Usually, a core and a coil are connected to each pair of gaps, and a magnetic field generated in the core can generate a leakage magnetic field in the pair of gaps by supplying a current pulse to the coil. When forming a servo pattern, a magnetic pattern corresponding to the pair of gaps can be transferred to the magnetic tape by inputting a current pulse while running the magnetic tape on the servo write head, thereby forming the servo pattern. The width of each gap can be appropriately set according to the density of the servo pattern to be formed. The width of each gap can be set, for example, to 1 μm or less, 1 to 10 μm, or 10 μm or more.
[0141] Before forming a servo pattern on the magnetic tape, the magnetic tape is usually subjected to a demagnetization (erase) process. This erase process can be performed by applying a uniform magnetic field to the magnetic tape using a direct current magnet or an alternating current magnet. There are two types of erase processes: DC (Direct Current) erase and AC (Alternating Current) erase. AC erase is performed by gradually lowering the strength of the magnetic field applied to the magnetic tape while reversing the direction of the magnetic field. On the other hand, DC erase is performed by applying a unidirectional magnetic field to the magnetic tape. There are two more methods of DC erase. The first method is horizontal DC erase, which applies a unidirectional magnetic field along the longitudinal direction of the magnetic tape. The second method is vertical DC erase, which applies a unidirectional magnetic field along the thickness direction of the magnetic tape. The erase process may be performed on the entire magnetic tape, or may be performed for each servo band of the magnetic tape.
[0142] The direction of the magnetic field of the formed servo pattern is determined according to the direction of erasure. For example, when the magnetic tape is subjected to horizontal DC erasure, the servo pattern is formed so that the direction of the magnetic field is opposite to the direction of erasure. This makes it possible to increase the output of the servo signal obtained by reading the servo pattern. As shown in JP2012-53940A, when the magnetic pattern is transferred to the magnetic tape that has been vertically DC erased using the above gap, the servo signal obtained by reading the formed servo pattern has a unipolar pulse shape. On the other hand, when the magnetic pattern is transferred to the magnetic tape that has been horizontally DC erased using the above gap, the servo signal obtained by reading the formed servo pattern has a bipolar pulse shape.
[0143] <Vertical squareness ratio> In one embodiment, the squareness ratio of the magnetic tape in the perpendicular direction can be, for example, 0.55 or more, and from the viewpoint of improving the electromagnetic conversion characteristics, it is preferably 0.60 or more, and more preferably 0.65 or more. The upper limit of the squareness ratio is, in principle, 1.00 or less. The squareness ratio of the magnetic tape in the perpendicular direction can be 1.00 or less, and can be 0.95 or less, 0.90 or less, 0.85 or less, or 0.80 or less. It is preferable that the squareness ratio of the magnetic tape in the perpendicular direction is large from the viewpoint of improving the electromagnetic conversion characteristics. The squareness ratio of the magnetic tape in the perpendicular direction can be controlled by a known method such as carrying out a perpendicular orientation process.
[0144] In the present invention and this specification, the "perpendicular squareness" refers to the squareness measured in the perpendicular direction of the magnetic tape. The "perpendicular direction" described in relation to the squareness is the direction perpendicular to the magnetic layer surface, and can also be called the thickness direction. In the present invention and this specification, the perpendicular squareness is determined by the following method. A sample piece of a size that can be introduced into a vibration sample magnetometer is cut out from the magnetic tape to be measured. A magnetic field is applied to this sample piece in a vertical direction (perpendicular to the magnetic layer surface) using a vibration sample magnetometer at a maximum applied magnetic field of 3979 kA / m, a measurement temperature of 296 K, and a magnetic field sweep speed of 8.3 kA / m / sec, and the magnetization strength of the sample piece against the applied magnetic field is measured. The measured value of the magnetization strength is obtained as a value after demagnetization field correction and a value obtained by subtracting the magnetization of the sample probe of the vibration sample magnetometer as background noise. When the magnetization strength at the maximum applied magnetic field is Ms and the magnetization strength at zero applied magnetic field is Mr, the squareness ratio SQ is a value calculated as SQ=Mr / Ms. The measurement temperature refers to the temperature of the sample piece, and by setting the ambient temperature around the sample piece to the measurement temperature, the temperature equilibrium is established and the temperature of the sample piece can be set to the measurement temperature.
[0145] [Magnetic tape cartridge] One aspect of the present invention relates to a magnetic tape cartridge including the above-mentioned magnetic tape.
[0146] The details of the magnetic tape contained in the magnetic tape cartridge are as described above. The magnetic tape cartridge can be mounted in a magnetic tape device equipped with a magnetic head and used to record and / or reproduce data.
[0147] In a magnetic tape cartridge, the magnetic tape is generally accommodated inside the cartridge body in a state where it is wound around a reel. The reel is provided rotatably inside the cartridge body. As the magnetic tape cartridge, a single-reel type magnetic tape cartridge having one reel inside the cartridge body and a twin-reel type magnetic tape cartridge having two reels inside the cartridge body are widely used. When a single-reel type magnetic tape cartridge is loaded into a magnetic tape device for recording and / or reproducing data on the magnetic tape, the magnetic tape is pulled out from the magnetic tape cartridge and wound around the reel on the magnetic tape device side. A magnetic head is disposed on the magnetic tape transport path from the magnetic tape cartridge to the take-up reel. The magnetic tape is fed and wound between the reel (supply reel) on the magnetic tape cartridge side and the reel (take-up reel) on the magnetic tape device side. For example, during this time, the magnetic head comes into contact with and slides on the surface of the magnetic layer of the magnetic tape, thereby recording and / or reproducing data. In contrast, a dual-reel magnetic tape cartridge is provided with both a supply reel and a take-up reel inside the magnetic tape cartridge.
[0148] In one embodiment, the magnetic tape cartridge may include a cartridge memory. The cartridge memory may be, for example, a non-volatile memory, and in one embodiment, head tilt angle adjustment information is already recorded or head tilt angle adjustment information is recorded. The head tilt angle adjustment information is information for adjusting the head tilt angle while the magnetic tape is running in the magnetic tape device. For example, the head tilt angle adjustment information may record the value of the servo band interval at each position in the longitudinal direction of the magnetic tape when data is recorded. For example, when reproducing data recorded on the magnetic tape, the value of the servo band interval is measured during reproduction, and the head tilt angle can be changed by the control device of the magnetic tape device so that the absolute value of the difference between the servo band interval at the same longitudinal position recorded in the cartridge memory during recording approaches 0. The head tilt angle may be, for example, the angle θ described above.
[0149] The magnetic tape and magnetic tape cartridge can be suitably used in a magnetic tape device (in other words, a magnetic recording and reproducing system) that records and / or reproduces data at different head tilt angles. In one embodiment of such a magnetic tape device, the head tilt angle can be changed while the magnetic tape is running to record and / or reproduce data. For example, the head tilt angle can be changed according to dimensional information in the width direction of the magnetic tape acquired while the magnetic tape is running. In another embodiment, the head tilt angle is changed from the head tilt angle in a certain recording and / or reproduction to the head tilt angle in the next and subsequent recording and / or reproduction, and the head tilt angle is fixed without being changed during the magnetic tape running for each recording and / or reproduction.
[0150] [Magnetic tape device] One aspect of the present invention relates to a magnetic tape device including the magnetic tape. In the magnetic tape device, data can be recorded on the magnetic tape and / or data recorded on the magnetic tape can be reproduced, for example, by contacting and sliding a magnetic head against the surface of the magnetic layer of the magnetic tape.
[0151] In one embodiment, the magnetic tape is treated as a removable medium (so-called exchangeable medium), and a magnetic tape cartridge containing the magnetic tape is inserted into and removed from a magnetic tape device, whereas in another embodiment, the magnetic tape is not treated as an exchangeable medium, and the magnetic tape is wound on a reel of a magnetic tape device equipped with a magnetic head, and the magnetic tape is stored in the magnetic tape device.
[0152] In the present invention and this specification, the term "magnetic tape device" refers to a device that can perform at least one of recording data on a magnetic tape and reproducing data recorded on a magnetic tape. Such a device is generally called a drive.
[0153] <Magnetic head> The magnetic tape device may include a magnetic head. The configuration of the magnetic head and the angle θ, which is the head tilt angle, are as described above with reference to Figs. 5 to 7. When the magnetic head includes a reproducing element, the reproducing element is preferably a magnetoresistive (MR: Magnetoresistive) element capable of reading information recorded on a magnetic tape with good sensitivity. As the MR element, various known MR elements (for example, a GMR (Giant Magnetoresistive) element, a TMR (Tunnel Magnetoresistive) element, etc.) can be used. Hereinafter, a magnetic head that records data and / or reproduces recorded data is also referred to as a "recording and reproducing head". An element for recording data (recording element) and an element for reproducing data (reproducing element) are collectively referred to as a "magnetic head element".
[0154] When recording data and / or reproducing recorded data, tracking can be performed using servo signals first. That is, by making the servo signal reading element follow a specific servo track, the magnetic head element can be controlled to pass over the target data track. The data track is moved by changing the servo track read by the servo signal reading element in the tape width direction. The recording / reproducing head can also record and / or reproduce data on other data bands by using the UDIM information described above to move the servo signal reading element to a specific servo band and start tracking on that servo band.
[0155] FIG. 9 shows an example of the arrangement of data bands and servo bands. In FIG. 9, a plurality of servo bands 1 are arranged on the magnetic layer of the magnetic tape MT, sandwiched between guide bands 3. A plurality of regions 2 sandwiched between two servo bands are data bands. A servo pattern is a magnetized region, and is formed by magnetizing a specific region of the magnetic layer with a servo write head. The region magnetized by the servo write head (the position where the servo pattern is formed) is determined by a standard. For example, in an LTO Ultrium format tape, which is an industry standard, a plurality of servo patterns inclined with respect to the tape width direction are formed on the servo band during the manufacturing of the magnetic tape, as shown in FIG. 10. More specifically, in FIG. 10, a servo frame SF on the servo band 1 is composed of a servo subframe 1 (SSF1) and a servo subframe 2 (SSF2). The servo subframe 1 is composed of an A burst (symbol A in FIG. 10) and a B burst (symbol B in FIG. 10). The A burst is composed of servo patterns A1 to A5, and the B burst is composed of servo patterns B1 to B5. On the other hand, the servo subframe 2 is composed of a C burst (symbol C in FIG. 10) and a D burst (symbol D in FIG. 10). The C burst is composed of servo patterns C1 to C4, and the D burst is composed of servo patterns D1 to D4. Such 18 servo patterns are arranged in a subframe arranged in a 5, 5, 4, 4 arrangement in a set of 5 and 4, and are used to identify a servo frame. For the sake of explanation, one servo frame is shown in FIG. 10. However, in reality, a plurality of servo frames are arranged in the running direction in each servo band on the magnetic layer of a magnetic tape where head tracking of the timing-based servo method is performed. In FIG. 10, the arrow indicates the magnetic tape running direction. For example, an LTO Ultrium format tape usually has 5000 or more servo frames per meter of tape length in each servo band on the magnetic layer.
[0156] In one embodiment, in the magnetic tape device, the head tilt angle can be changed while the magnetic tape is running inside the magnetic tape device. The head tilt angle is, for example, the angle θ that the axis of the element array makes with respect to the width direction of the magnetic tape. The angle θ is as described above. For example, by providing an angle adjustment unit that adjusts the angle of the magnetic head module in the recording / reproducing head unit of the magnetic head, the angle θ can be variably adjusted while the magnetic tape is running. Such an angle adjustment unit can include, for example, a rotation mechanism that rotates the module. Publicly known technology can be applied to the angle adjustment unit.
[0157] Regarding the head tilt angle during magnetic tape running, if the magnetic head includes multiple modules, the angle θ described with reference to Figures 5 to 7 can be specified for randomly selected modules. initial can be set to 0° or more or greater than 0°. initial The larger the angle θ, the larger the change in the effective distance between the servo signal reading elements becomes, and therefore it is preferable in terms of the ability to adjust the effective distance between the servo signal reading elements in response to the change in the width direction of the magnetic tape. initial is preferably 1° or more, more preferably 5° or more, and even more preferably 10° or more. On the other hand, with regard to the angle (generally called the "wrap angle") formed between the magnetic layer surface and the contact surface of the magnetic head when the magnetic tape runs and comes into contact with the magnetic head, keeping the deviation in the tape width direction small is effective in increasing the uniformity in the tape width direction of the friction generated by contact between the magnetic head and the magnetic tape while the magnetic tape is running. Also, increasing the uniformity of the above-mentioned friction in the tape width direction is desirable from the viewpoint of the position tracking ability and running stability of the magnetic head. From the viewpoint of reducing the deviation in the tape width direction of the above-mentioned wrap angle, θ initial is preferably 45° or less, more preferably 40° or less, and even more preferably 35° or less.
[0158] Regarding the change in the angle θ during the magnetic tape running, while the magnetic tape is running in the magnetic tape device for recording data on the magnetic tape and / or for reproducing data recorded on the magnetic tape, the angle θ of the magnetic head is changed from θ at the start of the running initial When the angle θ changes from max and Δθ min The maximum value of the angle θ during the magnetic tape running is θ max and the minimum value is θ min Note that "max" is an abbreviation for maximum, and "min" is an abbreviation for minimum. Δθ max =θ max -θ initial Δθ min =θ initial -θ min
[0159] In one embodiment, Δθ can be more than 0.000°, and from the viewpoint of the ability to adjust the effective distance between the servo signal reading elements in response to the dimensional change in the width direction of the magnetic tape, Δθ is preferably 0.001° or more, and more preferably 0.010° or more. Also, from the viewpoint of the ease of ensuring synchronization of the recording data and / or reproduction data between the multiple magnetic head elements during recording and / or reproduction of data, Δθ is preferably 1.000° or less, more preferably 0.900° or less, even more preferably 0.800° or less, even more preferably 0.700° or less, and even more preferably 0.600° or less.
[0160] 6 and 7, the axis of the element array is inclined toward the magnetic tape running direction. However, the present invention is not limited to such an example. The present invention also includes an embodiment in which the axis of the element array in the above magnetic tape device is inclined toward the opposite direction to the magnetic tape running direction.
[0161] The head inclination angle θ when the magnetic tape starts to run initialcan be set by the control device of the magnetic tape device, etc. With regard to the head tilt angle during magnetic tape running, FIG. 11 is an explanatory diagram of a method for measuring the angle θ during magnetic tape running. The angle θ during magnetic tape running can be obtained, for example, by the following method. When the angle θ during magnetic tape running is obtained by the following method, the angle θ is changed in the range of 0 to 90° during magnetic tape running. That is, if the axis of the element array is tilted toward the magnetic tape running direction at the start of magnetic tape running, the element array is not tilted so that the axis of the element array is tilted toward the opposite direction to the magnetic tape running direction at the start of magnetic tape running during magnetic tape running, and if the axis of the element array is tilted toward the opposite direction to the magnetic tape running direction at the start of magnetic tape running, the element array is not tilted so that the axis of the element array is tilted toward the magnetic tape running direction at the start of magnetic tape running during magnetic tape running. The phase difference (i.e., time difference) ΔT between the playback signals of a pair of servo signal read elements 1 and 2 is measured. The measurement of ΔT can be performed by a measurement unit provided in the magnetic tape device. The configuration of such a measurement unit is publicly known. The distance L between the center of the servo signal read element 1 and the center of the servo signal read element 2 can be measured by an optical microscope or the like. When the running speed of the magnetic tape is v, the distance between the centers of the two servo signal read elements in the magnetic tape running direction is Lsinθ, and the relationship Lsinθ=v×ΔT holds. Therefore, the angle θ during magnetic tape running can be calculated by the formula "θ=arcsin(vΔT / L)". Note that the right diagram of FIG. 11 shows an example in which the axis of the element array is inclined toward the magnetic tape running direction. In this example, the phase difference (i.e., time difference) ΔT between the phase of the playback signal of the servo signal read element 1 and the phase of the playback signal of the servo signal read element 2 is measured. When the axis of the element array is tilted toward the opposite direction to the running direction of the magnetic tape, θ can be found by the above method, except that ΔT is measured as the phase difference (i.e., time difference) between the phase of the playback signal of servo signal read element 1 relative to the phase of the playback signal of servo signal read element 2. The measurement pitch of the angle θ, i.e., the measurement interval of the angle θ relative to the tape longitudinal direction, can be selected to be appropriate depending on the frequency of the tape width deformation relative to the tape longitudinal direction. As an example, the measurement pitch can be set to 250 μm.
[0162] <Magnetic tape device configuration> A magnetic tape device 10 shown in FIG. 12 controls a recording / reproducing head unit 12 in response to commands from a control device 11, and records and reproduces data on a magnetic tape MT. The magnetic tape device 10 has a configuration capable of detecting and adjusting tension applied in the longitudinal direction of the magnetic tape from spindle motors 17A, 17B that control the rotation of the magnetic tape cartridge reel and take-up reel, and their drive devices 18A, 18B. The magnetic tape device 10 has a configuration in which a magnetic tape cartridge 13 can be loaded. The magnetic tape device 10 has a cartridge memory read / write device 14 capable of reading from and writing to a cartridge memory 131 in the magnetic tape cartridge 13 . From the magnetic tape cartridge 13 attached to the magnetic tape device 10, the end or leader pin of the magnetic tape MT is pulled out by an automatic loading mechanism or manually, and the magnetic tape MT passes over the recording / playback head via guide rollers 15A and 15B with the magnetic layer surface in a direction facing the recording / playback head surface of the recording / playback head unit 12, and the magnetic tape MT is wound onto the take-up reel 16. The rotation and torque of spindle motors 17A and 17B are controlled by signals from control device 11, and magnetic tape MT runs at any speed and tension. Servo patterns formed in advance on the magnetic tape can be used to control the tape speed and head tilt angle. A tension detection mechanism may be provided between magnetic tape cartridge 13 and take-up reel 16 to detect tension. In addition to control by spindle motors 17A and 17B, tension control may also be performed using guide rollers 15A and 15B. The cartridge memory read / write device 14 is configured to be able to read and write information from and to the cartridge memory 131 in response to commands from the control device 11. As a communication method between the cartridge memory read / write device 14 and the cartridge memory 131, for example, the ISO (International Organization for Standardization) 14443 method can be adopted.
[0163] The control device 11 includes, for example, a control unit, a storage unit, a communication unit, and the like.
[0164] The recording and reproducing head unit 12 is composed of, for example, a recording and reproducing head, a servo tracking actuator that adjusts the position of the recording and reproducing head in the track width direction, a recording and reproducing amplifier 19, a connector cable for connecting to the control device 11, etc. The recording and reproducing head is composed of, for example, a recording element that records data on the magnetic tape, a reproducing element that reproduces the data on the magnetic tape, and a servo signal reading element that reads the servo signal recorded on the magnetic tape. One magnetic head is equipped with, for example, one or more of each of the recording element, reproducing element, and servo signal reading element. Alternatively, each element may be provided separately in a plurality of magnetic heads according to the running direction of the magnetic tape.
[0165] The recording / reproducing head unit 12 is configured to be capable of recording data onto the magnetic tape MT in response to a command from the control device 11. Also, the recording / reproducing head unit 12 is configured to be capable of reproducing the data recorded onto the magnetic tape MT in response to a command from the control device 11.
[0166] The control device 11 has a mechanism for determining the running position of the magnetic tape from the servo signals read from the servo bands while the magnetic tape MT is running, and for controlling the servo tracking actuator so that the recording element and / or the reproducing element are positioned at the target running position (track position). The control of the track position is performed, for example, by feedback control. The control device 11 has a mechanism for determining the servo band interval from the servo signals read from two adjacent servo bands while the magnetic tape MT is running. The control device 11 can store information on the determined servo band interval in a storage unit inside the control device 11, a cartridge memory 131, an external connected device, or the like. The control device 11 can also change the head tilt angle according to dimensional information in the width direction of the magnetic tape while it is running. This allows the effective distance between the servo signal reading elements to be close to or match the interval between the servo bands. The above dimensional information can be acquired by utilizing a servo pattern formed in advance on the magnetic tape. For example, in this way, while the magnetic tape is running in the magnetic tape device, the angle θ that the axis of the element array makes with respect to the width direction of the magnetic tape can be changed according to the dimensional information of the magnetic tape in the width direction acquired during the running. The head tilt angle can be adjusted, for example, by feedback control. Also, for example, the head tilt angle can be adjusted by the method described in JP2016-524774A (Patent Document 1) or US2019 / 0164573A1 (Patent Document 2). EXAMPLES
[0167] The present invention will be described below based on examples. However, the present invention is not limited to the embodiments shown in the examples. The "parts" and "%" described below indicate "parts by mass" and "% by mass", respectively. In addition, the steps and evaluations described below were carried out in an environment with a temperature of 23°C ± 1°C unless otherwise specified. The "eq" described below is an equivalent, and is a unit that cannot be converted to SI units.
[0168] [Ferromagnetic powder] In Table 1, "BaFe" is hexagonal barium ferrite powder (coercive force Hc: 196 kA / m, average particle size (average plate diameter): 24 nm).
[0169] In Table 1, "SrFe1" is a hexagonal strontium ferrite powder produced by the following method. SrCO 3 1707g, H 3 BO 3 687g, Fe 2 O 3 1120g, Al(OH) 3 45g, BaCO 3 24g, CaCO 3 13g, and Nd 2 O 3 The above was weighed out in an amount of 235 g and mixed in a mixer to obtain a raw material mixture. The obtained raw material mixture was melted in a platinum crucible at a melting temperature of 1390°C, and the melt was poured into a rod shape at about 6 g / sec by heating the tapping hole at the bottom of the platinum crucible while stirring the melt. The tapped liquid was rolled and quenched with a water-cooled twin roller to produce an amorphous body. 280 g of the produced amorphous body was placed in an electric furnace, heated to 635°C (crystallization temperature) at a heating rate of 3.5°C / min, and held at that temperature for 5 hours to precipitate (crystallize) hexagonal strontium ferrite particles. Next, the above-obtained crystallized product containing hexagonal strontium ferrite particles was coarsely crushed in a mortar, and 1000 g of zirconia beads with a particle size of 1 mm and 800 ml of 1% aqueous acetic acid solution were added to the glass bottle containing the crystallized product, and the mixture was dispersed for 3 hours using a paint shaker. The resulting dispersion was then separated from the beads and placed in a stainless steel beaker. The dispersion was left to stand at a liquid temperature of 100°C for 3 hours to dissolve the glass components, and then precipitated in a centrifuge and washed by repeated decantation, and dried for 6 hours in a heating furnace at a furnace temperature of 110°C to obtain hexagonal strontium ferrite powder. The average particle size of the hexagonal strontium ferrite powder obtained above is 18 nm, and the activation volume is 902 nm. 3 , the anisotropy constant Ku is 2.2×10 5 J / m 3, mass magnetization σs is 49A m 2 / kg. A 12 mg sample powder was taken from the hexagonal strontium ferrite powder obtained above, and this sample powder was partially dissolved under the dissolution conditions exemplified above. The elemental analysis of the filtrate obtained was performed using an ICP analyzer to determine the surface layer content of neodymium atoms. Separately, 12 mg of sample powder was taken from the hexagonal strontium ferrite powder obtained above, and this sample powder was completely dissolved under the dissolution conditions exemplified above. The elemental analysis of the filtrate obtained was performed using an ICP analyzer to determine the bulk content of neodymium atoms. The neodymium atom content (bulk content) relative to 100 atomic % of iron atoms in the hexagonal strontium ferrite powder obtained above was 2.9 atomic %. The surface layer content of neodymium atoms was 8.0 atomic %. The ratio of the surface layer content to the bulk content, "surface layer content / bulk content," was 2.8, confirming that neodymium atoms were unevenly distributed in the surface layers of the particles. It was confirmed that the powder obtained above exhibited a hexagonal ferrite crystal structure by scanning with CuKα radiation at a voltage of 45 kV and an intensity of 40 mA and measuring the X-ray diffraction pattern under the following conditions (X-ray diffraction analysis). The powder obtained above exhibited a magnetoplumbite-type (M-type) hexagonal ferrite crystal structure. The crystal phase detected by the X-ray diffraction analysis was a single phase of magnetoplumbite type. PANalytical X'Pert Pro diffractometer, PIXcel detector Soller slits for incident and diffracted beams: 0.017 radians Dispersion slit fixed angle: 1 / 4 degree Mask: 10mm Anti-scatter slit: 1 / 4 degree Measurement mode: Continuous Measurement time per step: 3 seconds Measurement speed: 0.017 degrees per second Measurement step: 0.05 degrees
[0170] In Table 1, "SrFe2" is a hexagonal strontium ferrite powder produced by the following method. SrCO 3 1725g, H 3 BO 3 666g, Fe 2 O 3 1332g, Al(OH) 3 52g, CaCO 3 34g, BaCO 3 The above was weighed out in an amount of 141 g and mixed in a mixer to obtain a raw material mixture. The obtained raw material mixture was melted in a platinum crucible at a melting temperature of 1380°C, and the melt was poured into a rod shape at about 6 g / sec by heating the tapping hole at the bottom of the platinum crucible while stirring the melt. The tapped liquid was rolled and quenched with a water-cooled twin roller to produce an amorphous body. 280 g of the obtained amorphous body was placed in an electric furnace, heated to 645° C. (crystallization temperature), and held at that temperature for 5 hours to precipitate (crystallize) hexagonal strontium ferrite particles. Next, the above-obtained crystallized product containing hexagonal strontium ferrite particles was coarsely crushed in a mortar, and 1000 g of zirconia beads with a particle size of 1 mm and 800 ml of 1% aqueous acetic acid solution were added to the glass bottle containing the crystallized product, and the mixture was dispersed for 3 hours using a paint shaker. The resulting dispersion was then separated from the beads and placed in a stainless steel beaker. The dispersion was left to stand at a liquid temperature of 100°C for 3 hours to dissolve the glass components, and then precipitated in a centrifuge and washed by repeated decantation, and dried for 6 hours in a heating furnace at a furnace temperature of 110°C to obtain hexagonal strontium ferrite powder. The average particle size of the obtained hexagonal strontium ferrite powder was 19 nm, and the activation volume was 1102 nm. 3 , the anisotropy constant Ku is 2.0×10 5 J / m 3 , mass magnetization σs is 50A m 2 / kg.
[0171] In Table 1, "ε-iron oxide" is ε-iron oxide powder prepared by the following method. 8.3g of iron (III) nitrate nonahydrate, 1.3g of gallium (III) nitrate octahydrate, 190mg of cobalt (II) nitrate hexahydrate, 150mg of titanium (IV) sulfate, and 1.5g of polyvinylpyrrolidone (PVP) were dissolved in 90g of pure water, and 4.0g of ammonia solution with a concentration of 25% was added under the condition of an atmospheric temperature of 25°C while stirring with a magnetic stirrer in the air atmosphere, and the mixture was stirred for 2 hours at an atmospheric temperature of 25°C. A citric acid solution obtained by dissolving 1g of citric acid in 9g of pure water was added to the obtained solution, and the mixture was stirred for 1 hour. The powder precipitated after stirring was collected by centrifugation, washed with pure water, and dried in a heating furnace at an internal temperature of 80°C. 800g of pure water was added to the dried powder, and the powder was dispersed in water again to obtain a dispersion. The obtained dispersion was heated to 50°C, and 40g of 25% ammonia aqueous solution was added dropwise while stirring. After stirring for 1 hour while maintaining the temperature at 50°C, 14mL of tetraethoxysilane (TEOS) was added dropwise and stirred for 24 hours. 50g of ammonium sulfate was added to the obtained reaction solution, and the precipitated powder was collected by centrifugation, washed with pure water, and dried for 24 hours in a heating furnace with an internal temperature of 80°C to obtain a precursor of ferromagnetic powder. The obtained precursor of the ferromagnetic powder was placed in a heating furnace at an internal temperature of 1000° C. in an air atmosphere and subjected to a heat treatment for 4 hours. The heat-treated ferromagnetic powder precursor was placed in a 4 mol / L aqueous solution of sodium hydroxide (NaOH), and the liquid temperature was maintained at 70°C while stirring for 24 hours, thereby removing the impurity silicate compound from the heat-treated ferromagnetic powder precursor. Thereafter, the silicic acid compound was removed by centrifugation, and the ferromagnetic powder was collected and washed with pure water to obtain a ferromagnetic powder. The composition of the obtained ferromagnetic powder was confirmed by inductively coupled plasma-optical emission spectrometry (ICP-OES), and it was found to be Ga, Co, and Ti substituted ε-iron oxide (ε-Ga 0.28 Co 0.05 Ti 0.05 Fe 1.62 O 3In addition, X-ray diffraction analysis was performed under the same conditions as those described above for SrFe1, and it was confirmed from the peaks in the X-ray diffraction pattern that the obtained ferromagnetic powder had a single-phase ε-phase crystal structure (ε-iron oxide crystal structure) that did not contain α-phase or γ-phase crystal structures. The average particle size of the obtained ε-iron oxide powder was 12 nm, and the activation volume was 746 nm. 3 , the anisotropy constant Ku is 1.2×10 5 J / m 3 , mass magnetization σs is 16A m 2 / kg.
[0172] The activation volume and anisotropy constant Ku of the above hexagonal strontium ferrite powder and ε-iron oxide powder were determined for each ferromagnetic powder by the method described above using a vibrating sample magnetometer (manufactured by Toei Kogyo Co., Ltd.). Moreover, the mass magnetization σs is a value measured at a magnetic field strength of 15 kOe using a vibrating sample magnetometer (manufactured by Toei Kogyo Co., Ltd.).
[0173] [Nonmagnetic support] In Table 1, "PEN" denotes a polyethylene naphthalate substrate and "PA" denotes an aromatic polyamide substrate.
[0174] [Non-magnetic powder for backcoat layer] In the examples and comparative examples in which the "average plate diameter of non-magnetic powder" and "average plate thickness of non-magnetic powder" are listed in the "Backcoat layer" column in Table 1, the backcoat layer was formed using a non-magnetic powder composed of plate-like particles whose average plate diameter and average plate thickness were the values listed in Table 1. These non-magnetic powders were prepared by the method described below. The metal hydroxide and water were mixed in a closed container (mixing time and molar concentration of the metal hydroxide aqueous solution: see Table 1). The mixed aqueous solution was heated for 10 days in an autoclave with the internal temperature set to 270° C. After heating, the generated particles were collected by centrifugation. In this manner, non-magnetic powders were prepared. Alumina powder was prepared by using aluminum hydroxide as the metal hydroxide, zirconia powder was prepared by using zirconium hydroxide, and ceria powder was prepared by using cerium hydroxide.
[0175] In Table 1, "CS" in the "Type of non-magnetic powder" column of the "Backcoat layer" column is an abbreviation for colloidal silica. The colloidal silica particles had a spherical or elliptical shape.
[0176] In Table 1, the "average plate diameter of non-magnetic powder," "average plate thickness of non-magnetic powder," and "average particle size of non-magnetic powder" listed in the "Backcoat layer" column were measured using a Hitachi H-9000 transmission electron microscope and Carl Zeiss KS-400 image analysis software, and were determined as described above.
[0177] [Example 1] (1) Formulation of the composition for forming the magnetic layer (Magnetic liquid) Ferromagnetic powder (see Table 1): 100.0 parts SO 3 Sodium-containing polyurethane resin: 14.0 parts Weight average molecular weight: 70,000, SO 3 Sodium group: 0.4 meq / g Cyclohexanone: 150 parts Methyl ethyl ketone: 150 parts (Abrasive Liquid A) Alumina abrasive (average particle size: 100 nm): 3.0 parts Sulfonic acid group-containing polyurethane resin: 0.3 parts Weight average molecular weight: 70,000, SO 3 Sodium group: 0.3 meq / g Cyclohexanone: 26.7 parts (Abrasive liquid B) Diamond abrasive (average particle size: 100 nm): 1.0 part Sulfonic acid group-containing polyurethane resin: 0.1 parts Weight average molecular weight: 70,000, SO3 Sodium group: 0.3 meq / g Cyclohexanone: 26.7 parts (Silica sol) Colloidal silica (average particle size: 100 nm): 0.2 parts Methyl ethyl ketone: 1.4 parts (Other Ingredients) Stearic acid: 2.0 parts Butyl stearate: 10.0 parts Polyisocyanate (Coronate, manufactured by Nippon Polyurethane Co., Ltd.): 2.5 parts Cyclohexanone: 200.0 parts Methyl ethyl ketone: 200.0 parts
[0178] (2) Formulation of the composition for forming the nonmagnetic layer α-Iron oxide powder (average particle volume: see Table 1): 100.0 parts Carbon black (average particle size: 20 nm, pH: see Table 1): 25.0 parts SO 3 Sodium-containing polyurethane resin: 18.0 parts Weight average molecular weight: 70,000, SO 3 Sodium group: 0.2 meq / g Stearic acid: 1.0 parts Cyclohexanone: 300.0 parts Methyl ethyl ketone: 300.0 parts
[0179] (3) Formulation of the composition for forming the backcoat layer Non-magnetic powder (see Table 1 for details): 100.0 parts SO 3 Na-containing polyurethane resin (SO 3 Na group: 70eq / ton): 20.0 parts OSO 3 K-group-containing polyvinyl chloride resin (OSO 3 K group: 70eq / ton): 30.0 parts Polyethyleneimine (manufactured by Nippon Shokubai, number average molecular weight 600): See Table 1 Stearic acid: see Table 1 Cyclohexanone: 140.0 parts Methyl ethyl ketone: 170.0 parts Butyl stearate: 2.0 parts Stearic acid amide: 0.1 parts
[0180] (4) Preparation of compositions for forming each layer For the magnetic layer forming composition, the above components of the magnetic liquid were dispersed for 24 hours using a batch type vertical sand mill to prepare the magnetic liquid. Zirconia beads with a bead diameter of 0.5 mm were used as the dispersion beads. Regarding the polishing compound liquids, the above-mentioned components of polishing compound liquid A and polishing compound liquid B were dispersed for 24 hours using a batch-type ultrasonic device (20 kHz, 300 W) to obtain polishing compound liquid A and polishing compound liquid B, respectively. The magnetic liquid, abrasive liquid A, and abrasive liquid B were mixed with the above-mentioned silica sol and other components, and then dispersed for 30 minutes using a batch-type ultrasonic device (20 kHz, 300 W).The mixture was then filtered using a filter with a pore size of 0.5 μm to prepare a magnetic layer-forming composition. The non-magnetic layer-forming composition was prepared by dispersing the above components for 24 hours using a batch-type vertical sand mill. Zirconia beads with a bead diameter of 0.1 mm were used as the dispersion beads. The obtained dispersion was filtered using a filter with a pore size of 0.5 μm to prepare the non-magnetic layer-forming composition. The composition for forming a backcoat layer was prepared by kneading the above components with a continuous kneader and then dispersing them with a sand mill (dispersion time: see Table 1). 40.0 parts of polyisocyanate (Coronate L, manufactured by Nippon Polyurethane Industry Co., Ltd.) and 1000.0 parts of methyl ethyl ketone were added to the obtained dispersion, and then filtered with a filter having a pore size of 1 μm to prepare a composition for forming a backcoat layer.
[0181] (5) Manufacturing of magnetic tapes and magnetic tape cartridges A magnetic tape was produced according to the manufacturing process shown in Figure 8. More specifically, the process was as follows. A nonmagnetic support of the thickness and type shown in Table 1 was sent out from a sending section, and a coating layer was formed by applying a nonmagnetic layer-forming composition to one surface in a first coating section so that the thickness after drying would be 0.7 μm. The formed coating layer was passed through a cooling zone adjusted to an atmospheric temperature of 0° C. while still wet to carry out a cooling step (cooling zone residence time: 1 second), and then passed through a first heat treatment zone with a drying temperature (atmospheric temperature, the same applies below) of 105° C. to carry out a heat drying step, thereby forming a nonmagnetic layer. Thereafter, in the second coating section, the magnetic layer-forming composition prepared above was coated on the non-magnetic layer so that the thickness after drying would be 0.1 μm to form a coating layer. While this coating layer was still wet, a magnetic field with a magnetic field strength of 0.5 T was applied in the direction perpendicular to the surface of the coating layer of the magnetic layer-forming composition in the orientation zone to perform a vertical orientation treatment, and then the coating layer was dried in the second heat treatment zone at a drying temperature of 105° C. Thereafter, in a third coating section, the composition for forming a backcoat layer prepared above was applied to the surface of the non-magnetic support opposite to the surface on which the non-magnetic layer and magnetic layer were formed, to form a coating layer having a thickness after drying of 0.3 μm, and the formed coating layer was dried in a third heat treatment zone at a drying temperature of 105° C. Thereafter, the sheet was subjected to a calendering treatment (surface smoothing treatment) under the calendering conditions shown in Table 1 using a calender roll consisting of only a metal roll. Thereafter, the sample was subjected to a heat treatment for 36 hours in an atmosphere at 70° C. After the heat treatment, the sample was slit into a 1 / 2 inch width to prepare a magnetic tape. In a demagnetized state, the magnetic layer of the magnetic tape thus produced was recorded with a servo signal by a commercially available servo writer on the magnetic layer, thereby obtaining a magnetic tape having a data band, a servo band, and a guide band in an arrangement conforming to the LTO (Linear Tape-Open) Ultrium format, and a servo pattern (timing-based servo pattern) on the servo band in an arrangement and shape conforming to the LTO Ultrium format. The servo pattern thus formed is a servo pattern conforming to the descriptions in JIS (Japanese Industrial Standards) X6175:2006 and Standard ECMA-319 (June 2001). The total number of servo bands is 5, and the total number of data bands is 4. In this way, a magnetic tape (length 960 m) on which a servo signal was recorded was produced.
[0182] Whether the backcoat layer of a magnetic tape contains a compound containing an ammonium salt structure of an alkyl ester anion represented by formula 1, which is formed from polyethyleneimine and stearic acid, can be confirmed by the following method. A sample is cut out from the magnetic tape, and the surface of the backcoat layer (measurement area: 300 μm × 700 μm) is subjected to X-ray photoelectron spectroscopy using an ESCA device. In detail, a wide scan measurement is performed using the ESCA device under the following measurement conditions. In the measurement results, peaks are confirmed at the position of the binding energy of the ester anion and the position of the binding energy of the ammonium cation. Equipment: Shimadzu AXIS-ULTRA Excitation X-ray source: Monochromated Al-Kα radiation Scan range: 0~1200eV Pass energy: 160 eV Energy resolution: 1eV / step Acquisition time: 100ms / step Number of times: 5 In addition, a sample piece of 3 cm in length was cut out from the magnetic tape, and the surface of the backcoat layer was measured with an attenuated total reflection-Fourier transform-infrared spectrometer (ATR-FT-IR) (reflection method). - The wave number corresponding to the absorption of -1 or 1430cm -1 ), and the wavenumber corresponding to the absorption of the ammonium cation (2400 cm -1 ) absorption is confirmed.
[0183] [Examples 2 to 19, Comparative Examples 1 to 11] A magnetic tape was obtained by the method described in Example 1, except that the items shown in Table 1 were changed as shown in Table 1.
[0184] For each of the Examples and Comparative Examples, four magnetic tapes each having a length of 960 m were prepared and used for the following evaluations (1) to (4).
[0185] [Evaluation method] (1) Sci of the magnetic layer surface, σ in the width direction of Sci The following conditions were adopted as the AFM measurement conditions, and the Sci and the width direction σ of Sci on the magnetic layer surface of the magnetic tape were obtained by the method described above. The AFM data analysis software (Nanoscope Analysis) provided by BRUKER was used. An AFM (BRUKER Nanoscope 5) is used in peak force tapping mode to measure an area of 40 μm × 40 μm on the surface of the magnetic layer of the magnetic tape. A BRUKER SCANASYST-AIR probe is used, with a resolution of 512 pixels × 512 pixels and a scan speed of 512 seconds per screen (512 pixels × 512 pixels).
[0186] (2) Nonlinear component of tape width deformation For each of the magnetic tapes of the examples and comparative examples, the nonlinear component of the tape width deformation caused by storage for 10 days in an environment of a temperature of 60° C. and a relative humidity of 20% was measured by the method described above.
[0187] (3) Total thickness of magnetic tape (tape thickness) Ten tape samples (5 cm long) were cut out from any part of each magnetic tape of the Examples and Comparative Examples, and these tape samples were stacked to measure the thickness. The thickness was measured using a digital thickness meter with a Millimar 1240 compact amplifier and a Millimar 1301 inductive probe manufactured by MARH. The measured thickness was divided by 10 to obtain the value (thickness per tape sample) as the tape thickness. The tape thickness of each magnetic tape of Examples 1 to 16 and Comparative Examples 1 to 11 was 4.8 μm. The tape thickness of each magnetic tape of Examples 17 to 19 was as follows. Example 17: 4.7 μm, Example 18: 4.1 μm, Example 19: 3.5 μm. The thicknesses of the magnetic layer, nonmagnetic layer, nonmagnetic support and backcoat layer of each magnetic tape in the Examples and Comparative Examples were confirmed by cross-sectional observation as described above to be the thicknesses described above or shown in Table 1.
[0188] (4) Recording and playback performance The recording and reproducing performance of each of the magnetic tapes of the Examples and Comparative Examples was evaluated by the following method. The magnetic head used was equipped with a reproducing module including an element array having 10 or more channels of reproducing elements with a reproducing element width of 0.2 μm or less between a pair of servo signal reading elements, and a recording module including an element array having 10 or more channels of recording elements with a recording element width of 1.5 times or more between a pair of servo signal reading elements. In the element array, the distance between two adjacent elements (i.e., two adjacent reproducing elements and two adjacent recording elements) in the head width direction is 40 μm or more. The environment for recording and reproducing data was set to a temperature of 20 to 25°C and a relative humidity of 40 to 60%. A magnetic tape device with a magnetic tape and a magnetic head attached to a tape transport system (reel tester) was placed in this environment for more than 24 hours, and then data was recorded and reproduced. The recording and reproducing amplifier attached to the tape transport system of the magnetic tape device was the recording and reproducing amplifier described above for measuring the nonlinear component of tape width deformation. When recording and reproducing data, the servo following and dynamic track position control (change in head tilt angle) described above were performed. In detail, data recording and reproducing were performed as follows. Signals were recorded by the recording element while the magnetic tape was running at a constant speed of 5 m / sec. The bit sequence used for recording was a 255-bit pseudo random bit sequence (PRBS) generated according to the generating polynomial x^8+x^6+x^5+x^4+1. The symbol "^" indicates exponentiation. The linear recording density was 600 kbpi. The unit "kbpi" is the unit of linear recording density (cannot be converted to SI units). Shingle recording was performed on three or more tracks so that the difference in (PES1+PES2) / 2 between adjacent tracks was 1.5 times the playback track width. The magnetic pattern recorded on the magnetic tape is reproduced by the immediately succeeding reproducing element (i.e., the reproducing element with the same channel number), and the signal is amplified by the reproducing amplifier. The reproduced signal is processed by PLL (Phase Lock Loop) and AGC (Auto Gain Control), and then decoded into a bit sequence based on DD-NPML (Data Dependent Noise Predictive Maximum Likelihood) signal processing. The recorded bit sequence and the reproduced and decoded bit sequence are compared bit by bit, and if the two are different, a one-bit error is counted as having occurred. The data is compared over 10 Mbits, and the cumulative error bit count divided by 10 Mbits is defined as the bit error rate. It was confirmed that the bit error rate of the reproduced signal immediately after recording was 1 / 1000 or less in all channels. Next, the magnetic tape was stored for 10 days in an environment having a temperature of 60° C. and a relative humidity of 20% while being wound on the reel of the reel tester. After the above storage, the magnetic tape was removed from the storage environment and placed in the same magnetic tape device as the one used before storage in an environment with a temperature of 20 to 25°C and a relative humidity of 40 to 60% for 24 hours or more, and then the data tracks recorded before storage were played back (no recording was performed) in the same environment. At this time, playback was performed only for data tracks that had data tracks recorded on both sides. The bit error rate of all channels was calculated, and channels with a bit error rate of 1 / 100 or more were considered to be defective channels, and the recording and playback performance was evaluated according to the following evaluation criteria. (Evaluation Criteria) A: The ratio of defective channels to the total number of channels is less than 5%. B: The ratio of defective channels to the total number of channels is 5% or more and less than 10%. C: The ratio of defective channels to the total number of channels is 10% or more.
[0189] The above results are shown in Table 1 (Table 1-1 to Table 1-6).
[0190] [Table 1-1]
[0191] [Table 1-2]
[0192] [Table 1-3]
[0193] [Table 1-4]
[0194] [Table 1-5]
[0195] [Table 1-6]
[0196] As shown in Table 1, the magnetic tape of the embodiment showed superior recording and reproducing performance after being stored under an accelerated environment equivalent to long-term storage, compared to the magnetic tape of the comparative example. From this result, it can be confirmed that the magnetic tape of the embodiment contributed to improving the operational stability of the drive (magnetic tape device).
[0197] A magnetic tape was produced in the same manner as in Example 1, except that no perpendicular orientation treatment was performed during the production of the magnetic tape. A sample piece was cut out from the magnetic tape, and the squareness in the vertical direction of the sample piece was measured by the above-mentioned method using a vibrating sample magnetometer, TM-TRVSM5050-SMSL model, manufactured by Tamagawa Seisakusho, and was found to be 0.55. The perpendicular squareness ratio of a sample piece cut out from the magnetic tape of Example 1 was similarly determined and was found to be 0.65.
[0198] The two magnetic tapes were each attached to a 1 / 2 inch reel tester, and the electromagnetic conversion characteristics (SNR: Signal-to-Noise Ratio) were evaluated by the following method. As a result, the magnetic tape of Example 1 had an SNR value 4 dB higher than that of the magnetic tape produced without the vertical orientation treatment. In an environment with a temperature of 23°C and a relative humidity of 50%, 10 passes of recording and reproduction were performed with a tension of 0.7 N (Newton) applied in the longitudinal direction of the magnetic tape. The relative speed between the magnetic tape and the magnetic head was 6 m / sec. Recording was performed using a MIG (Metal-in-gap) head (gap length 0.15 μm, track width 1.0 μm) as the recording head, and the recording current was set to the optimal recording current for each magnetic tape. Reproduction was performed using a GMR (Giant-magnetoresistive) head (element thickness 15 nm, shield spacing 0.1 μm, reproducing element width 0.8 μm) as the reproducing head. The head tilt angle was 0°. A signal with a linear recording density of 300 kfci was recorded, and the reproduced signal was measured with a spectrum analyzer manufactured by Shibasoku. The unit kfci is a unit of linear recording density (not convertible to SI units). The signal was used at a portion where the signal was sufficiently stable after the magnetic tape started running. [Industrial Applicability]
[0199] One aspect of the present invention is useful in various data storage technical fields.
Claims
1. A magnetic tape having a non-magnetic support and a magnetic layer containing ferromagnetic powder, The surface of the magnetic layer is measured using an atomic force microscope, and Sci calculated by the following formula A is 1.40 or more and 1.60 or less, and a magnetic tape in which the standard deviation σ of Sci in the width direction of the surface of the magnetic layer is 0.05 or less; [0010] In formula A, Sq is the root mean square height Sq as defined in ISO 25178; Vv(h 0.05 ) - Vv(h 0.8 ) is the void volume in the region where the areal load factor is 5% or more and 80% or less on the bearing curve, A is the area of the measurement region.
2. 2. The magnetic tape of claim 1, wherein the standard deviation σ of Sci is 0.04 or less.
3. 2. The magnetic tape according to claim 1, further comprising a non-magnetic layer between the non-magnetic support and the magnetic layer, the non-magnetic layer containing a non-magnetic powder.
4. The non-magnetic powder of the non-magnetic layer has an average particle volume of 2.0×10 -6 μm 3 4. The magnetic tape according to claim 3, comprising the following Fe-based inorganic oxide powder:
5. 4. The magnetic tape according to claim 3, wherein the non-magnetic powder in the non-magnetic layer contains carbon black having a pH of 9.0 or less.
6. 4. The magnetic tape according to claim 3, wherein the nonmagnetic layer has a thickness of 0.1 μm or more and 0.7 μm or less.
7. 2. The magnetic tape according to claim 1, further comprising a backcoat layer containing a nonmagnetic powder on the surface of said nonmagnetic support opposite to the surface having said magnetic layer.
8. 8. The magnetic tape according to claim 7, wherein the non-magnetic powder in the backcoat layer includes non-magnetic powder having an average plate diameter of 50 nm or more and 1000 nm or less and an average plate thickness of 12 nm or less.
9. 2. The magnetic tape of claim 1, wherein the tape thickness is 5.2 μm or less.
10. 2. The magnetic tape of claim 1, wherein the tape thickness is 5.0 μm or less.
11. 2. The magnetic tape of claim 1, wherein the perpendicular squareness of the magnetic tape is 0.60 or more.
12. 2. The magnetic tape of claim 1, wherein the perpendicular squareness of the magnetic tape is 0.65 or greater.
13. 2. The magnetic tape of claim 1, wherein the non-magnetic support is an aromatic polyamide support.
14. The standard deviation σ of the Sci is 0.04 or less, a non-magnetic layer containing a non-magnetic powder between the non-magnetic support and the magnetic layer, The non-magnetic powder of the non-magnetic layer has an average particle volume of 2.0×10 -6 μm 3 The composition comprises the following Fe-based inorganic oxide powder and carbon black having a pH of 9.0 or less: the thickness of the nonmagnetic layer is 0.1 μm or more and 0.7 μm or less, a backcoat layer containing a nonmagnetic powder on the surface side of the nonmagnetic support opposite to the surface side having the magnetic layer, the non-magnetic powder of the backcoat layer includes non-magnetic powder having an average plate diameter of 50 nm or more and 1000 nm or less and an average plate thickness of 12 nm or less; The tape thickness is 5.0 μm or less, and 2. The magnetic tape of claim 1, wherein the perpendicular squareness of the magnetic tape is 0.65 or greater.
15. A magnetic tape cartridge comprising the magnetic tape according to any one of claims 1 to 14.
16. A magnetic tape device comprising the magnetic tape according to any one of claims 1 to 14.
17. Further comprising a magnetic head; the magnetic head has a module including an element array having a plurality of magnetic head elements between a pair of servo signal reading elements; and 17. The magnetic tape device according to claim 16, wherein the angle θ that the axis of the element array makes with respect to the width direction of the magnetic tape is changed while the magnetic tape is running inside the magnetic tape device.
Citation Information
Patent Citations
Magnetic Head, System, and Program Having an Offset Array
JP2016524774A
magnetic recording cartridge
JP6590102B1
Magnetic recording head having longitudinally spaced offset arrays
US20190164573A1